Gas barrier coating material and gas barrier laminate

Through low-temperature and short-time heat treatment and a combination of polycarboxylic acids, polyamine compounds and Zn compounds in specific proportions, the problems of cracks and low productivity during post-processing of gas barrier materials are solved, and more efficient gas barrier properties and Longer pot life.

CN119343418APending Publication Date: 2025-01-21RM TOHCELLO CO LTD

Patent Information

Application Number
CN202380043690.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-02
Filing Date
2023-05-31
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing gas barrier materials are prone to cracks during post-processing, resulting in a decrease in gas barrier property. High temperature and long-term heating lead to a decrease in productivity, and the decrease in crosslinking degree also affects barrier property.

Method used

Through low-temperature and short-time heat treatment, combined with the ratio of polycarboxylic acids, polyamine compounds and Zn compounds, cross-linking agents such as epoxy silane compounds, carbodiimide compounds and isocyanate compounds are used to form a dense gas barrier layer.

Benefits of technology

The productivity and barrier properties balance of the gas barrier material are improved, and the peel strength and pot life of the gas barrier layer are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343418A_ABST
    Figure CN119343418A_ABST
Patent Text Reader

Abstract

A coating material for gas barrier, which contains a polycarboxylic acid, a polyamine compound, and a Zn compound, and wherein (the number of moles of Zn compound in the coating material for gas barrier) / (the number of moles of-COO-groups contained in the polycarboxylic acid in the coating material for gas barrier) in the coating material for gas barrier is from 0.40 to 0.70 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a gas barrier coating material and a gas barrier laminate. Background Art

[0002] As the gas barrier material, a laminated body in which an inorganic layer as a gas barrier layer is provided on a base layer is used.

[0003] However, the inorganic layer cannot withstand friction and the like, and such a gas barrier laminate may have cracks generated in the inorganic layer due to friction or stretching during post-processing such as printing, lamination, or filling of contents, thereby reducing the gas barrier properties.

[0004] Therefore, as a gas barrier material, a laminated body using an organic layer as a gas barrier layer is also used.

[0005] As a gas barrier material using an organic layer as a gas barrier layer, a laminate having a gas barrier layer formed from a mixture containing a polycarboxylic acid and a polyamine compound is known. As technologies related to such gas barrier laminates, for example, the technologies described in Patent Documents 1 and 2 can be cited.

[0006] Patent Document 1 (Japanese Patent Application Publication No. 2005-225940) discloses a gas barrier film having a gas barrier layer formed from a polycarboxylic acid and a polyamine and / or a polyol, wherein the degree of crosslinking of the polycarboxylic acid is 40% or more. The document states that such a gas barrier film has excellent gas barrier properties under high humidity conditions as well as under low humidity conditions.

[0007] Patent document 2 (Japanese Patent Application Publication No. 2013-10857) discloses a film obtained by coating at least one side of a substrate formed of a plastic film with the following mixture, wherein the mixture is obtained by mixing polyamine and polycarboxylic acid in a weight ratio of polyamine / polycarboxylic acid = 12.5 / 87.5 to 27.5 / 72.5. The document states that such a gas barrier film has excellent gas barrier properties, especially oxygen barrier properties, even after boiling treatment, and has excellent flexibility, transparency, moisture resistance, chemical resistance, etc.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2005-225940

[0011] Patent Document 2: Japanese Patent Application Publication No. 2013-10857 Summary of the invention

[0012] Problems to be solved by the invention

[0013] The technical level required for various properties of gas barrier materials is gradually increasing. The inventors of the present application have studied conventional gas barrier materials such as those described in Patent Documents 1 and 2.

[0014] As a result, it was found that the gas barrier materials described in Patent Documents 1 and 2 require heating at a high temperature for a long time in order to crosslink the polycarboxylic acid and the polyamine, and thus productivity may be reduced.

[0015] It was also found that, for such gas barrier materials, if the heating temperature for crosslinking the polycarboxylic acid and the polyamine is lowered or the heating treatment time is shortened in order to improve productivity, the ratio of amide bonds formed by crosslinking the polycarboxylic acid and the polyamine may decrease, thereby reducing barrier properties.

[0016] Based on these, the inventors of the present application have found that from the perspective of improving productivity and barrier properties in a well-balanced manner, there is room for improvement in conventional gas barrier materials. So far, there are many technologies that focus on improving barrier properties, but so far no technology has been reported that improves barrier properties and productivity in a well-balanced manner.

[0017] A first aspect of the present invention has been made in view of the above circumstances, and provides a gas barrier coating material having an improved balance between productivity and barrier properties by heat treatment at low temperature and for a short time.

[0018] In addition, it has been found that in the gas barrier materials described in Patent Documents 1 and 2, the gas barrier layer may be separated from the base material layer, thereby reducing the gas barrier property.

[0019] Based on these, the inventors of the present application have found that conventional gas barrier materials have room for improvement from the viewpoint of improving barrier properties and peel strength in a well-balanced manner.

[0020] A second aspect of the present invention has been made in view of the above circumstances, and provides a gas barrier coating material having improved barrier properties and peel strength.

[0021] It is also found that the gas barrier materials described in Patent Documents 1 and 2 require heating at high temperatures for a long time in order to crosslink the polycarboxylic acid and the polyamine, and thus productivity may be reduced.

[0022] It was also clarified that, for such a gas barrier material, when the zinc (Zn) content is increased to improve the oxygen barrier property, and when the phosphate compound content is increased to improve the water vapor barrier property, although each barrier property is improved, Zn reacts with the phosphate compound in the coating liquid used to form the gas barrier material and precipitates, and the pot life of the coating liquid is sometimes shortened.

[0023] Based on these, the inventors of the present application have found that conventional gas barrier materials have room for improvement from the viewpoint of improving the barrier properties and the pot life of the coating liquid in a well-balanced manner.

[0024] The third aspect of the present invention has been made in view of the above circumstances, and provides a gas barrier coating material having an improved balance between barrier properties and pot life.

[0025] Means for solving problems

[0026] According to a first embodiment of the present invention, there are provided the following gas barrier coating material and gas barrier layered product.

[0027] [1] A gas barrier coating material comprising a polycarboxylic acid, a polyamine compound, and a Zn compound,

[0028] In the gas barrier coating material, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.40 or more and 0.70 or less.

[0029] [2] The gas barrier coating material according to [1] above, further comprising a crosslinking agent.

[0030] [3] The gas barrier coating material according to [2] above, wherein the crosslinking agent comprises one or more compounds selected from the group consisting of epoxysilane compounds, carbodiimide compounds, and isocyanate compounds.

[0031] [4] The gas barrier coating material according to any one of [1] to [3] above, wherein the polycarboxylic acid comprises one or more compounds selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.

[0032] [5] The gas barrier coating material according to any one of [1] to [4] above, wherein the polyamine compound comprises one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine).

[0033] [6] The gas barrier coating material according to any one of [1] to [5] above, further comprising a polyphosphoric acid compound or a salt thereof.

[0034] [7] The gas barrier coating material as described in [6] above, wherein the (number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (number of moles of COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.005 to 0.20.

[0035] [8] The gas barrier coating material as described in any one of [1] to [7] above, wherein the (number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) in the gas barrier coating material is 0.40 to 0.70.

[0036] [9] A gas barrier layered product comprising a substrate layer and a gas barrier layer provided on at least one surface of the substrate layer,

[0037] The gas barrier layer includes a cured product of the gas barrier coating material according to any one of [1] to [8] above.

[0038]

[10] The gas barrier layered product according to [9] above, wherein the thickness of the gas barrier layer is 0.05 μm to 10 μm.

[0039]

[11] The gas barrier layered product according to [9] or

[10] , further comprising an inorganic layer provided between the substrate layer and the gas barrier layer.

[0040]

[12] A gas barrier laminate as described in

[11] above, wherein the inorganic layer is a vapor-deposited film provided on the substrate layer, or when there is an intermediate layer between the substrate layer and the inorganic layer, it is a vapor-deposited film provided on the intermediate layer, and the inorganic layer is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum.

[0041] Moreover, according to a second embodiment of the present invention, there are provided a gas barrier coating material and a gas barrier laminate as described below.

[0042] [1] A gas barrier coating material comprising a polycarboxylic acid, a polyamine compound, and a Zn compound,

[0043] The cured product of the gas barrier coating material has a Zn composition ratio of 3.0 atomic % to 10.0 atomic % as measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA.

[0044] [2] The gas barrier coating material according to [1] above, further comprising a polyphosphoric acid compound or a salt thereof.

[0045] [3] The gas barrier coating material as described in [2] above, wherein, for the cured product of the gas barrier coating material, the P composition ratio measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA is 0.05 atomic% or more and 1.5 atomic% or less.

[0046] [4] The gas barrier coating material according to any one of [1] to [3] above, wherein the polycarboxylic acid comprises one or more compounds selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.

[0047] [5] The gas barrier coating material according to any one of [1] to [4] above, wherein the polyamine compound comprises one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine).

[0048] [6] The gas barrier coating material according to any one of [1] to [5] above, further comprising a crosslinking agent.

[0049] [7] The gas barrier coating material according to [6] above, wherein the crosslinking agent comprises one or more compounds selected from the group consisting of epoxysilane compounds, carbodiimide compounds, and isocyanate compounds.

[0050] [8] A gas barrier layered product comprising a substrate layer and a gas barrier layer provided on at least one surface of the substrate layer,

[0051] The gas barrier layer includes a cured product of the gas barrier coating material according to any one of [1] to [7] above.

[0052] [9] The gas barrier layered product according to [8] above, wherein the thickness of the gas barrier layer is from 0.05 μm to 10 μm.

[0053]

[10] The gas barrier layered product according to [8] or [9], further comprising an inorganic layer between the substrate layer and the gas barrier layer.

[0054]

[11] A gas barrier laminate as described in

[10] above, wherein the inorganic layer is a vapor-deposited film provided on the substrate layer, or when there is an intermediate layer between the substrate layer and the inorganic layer, it is a vapor-deposited film provided on the intermediate layer, and the inorganic layer is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum.

[0055] Moreover, according to the 3rd embodiment of this invention, the following gas barrier coating material and gas barrier layered product are provided.

[0056] [1] A gas barrier coating material comprising a polycarboxylic acid, a polyamine compound, a Zn compound, and a polyphosphoric acid compound or a salt thereof.

[0057] [2] The gas barrier coating material according to [1] above, wherein the ratio of (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.005 to 0.20.

[0058] [3] The gas barrier coating material according to [1] or [2] above, wherein the (number of moles of the Zn compound in the gas barrier coating material) / (number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.40 to 0.70.

[0059] [4] The gas barrier coating material as described in any one of [1] to [3] above, wherein the (number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) in the gas barrier coating material is 0.40 to 0.70.

[0060] [5] The gas barrier coating material according to any one of [1] to [4] above, wherein the polycarboxylic acid comprises one or more compounds selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.

[0061] [6] The gas barrier coating material according to any one of [1] to [5] above, wherein the polyamine compound comprises one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine).

[0062] [7] The gas barrier coating material according to any one of [1] to [6] above, further comprising a crosslinking agent.

[0063] [8] The gas barrier coating material according to [7] above, wherein the crosslinking agent comprises one or more compounds selected from the group consisting of epoxysilane compounds, carbodiimide compounds, and isocyanate compounds.

[0064] [9] A gas barrier coating material as described in any one of [1] to [8] above, wherein, for the cured product of the gas barrier coating material, the Zn composition ratio measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output power: 15 kV, 10 mA is 1.0 atomic % or more and 10.0 atomic % or less.

[0065]

[10] A gas barrier coating material as described in any one of [1] to [9] above, wherein, for the cured product of the gas barrier coating material, the P composition ratio measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output power: 15 kV, 10 mA is 0.05 atomic% or more and 1.5 atomic% or less.

[0066]

[11] A gas barrier layered product comprising a substrate layer and a gas barrier layer provided on at least one surface of the substrate layer,

[0067] The gas barrier layer includes a cured product of the gas barrier coating material according to any one of [1] to

[10] above.

[0068]

[12] The gas barrier layered product according to

[11] above, wherein the thickness of the gas barrier layer is 0.05 μm to 10 μm.

[0069]

[13] The gas barrier layered product according to

[11] or

[12] , further comprising an inorganic layer between the substrate layer and the gas barrier layer.

[0070]

[14] A gas barrier laminate as described in

[13] above, wherein the inorganic layer is a vapor-deposited film disposed on the substrate layer, or when there is an intermediate layer between the substrate layer and the inorganic layer, it is a vapor-deposited film disposed on the intermediate layer, and the inorganic layer is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum.

[0071] Effects of the Invention

[0072] According to the first embodiment of the present invention, it is possible to provide a gas barrier material having improved balance between productivity and barrier properties by heat treatment at low temperature and for a short time.

[0073] Moreover, according to the second embodiment of the present invention, a gas barrier coating material having improved barrier properties and peel strength can be provided.

[0074] Furthermore, according to the third embodiment of the present invention, a gas barrier coating material having an improved balance between barrier properties and pot life can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] [ Figure 1 ] is a cross-sectional view schematically showing an example of the structure of a gas barrier layered product in an embodiment. DETAILED DESCRIPTION

[0076] Hereinafter, each embodiment of the present invention will be described with reference to the drawings. It should be noted that the drawings are schematic diagrams and do not correspond to actual dimensional ratios.

[0077] In the present specification, unless otherwise specified, "-" between numbers in the text means above and below, including both ends.

[0078] In this specification, "(meth)acryl-" means at least one of "acryl-" and "methacryl-".

[0079] In the first to third embodiments of the present invention, the composition may contain each component alone or in combination of two or more components.

[0080] <First Embodiment>

[0081] The gas barrier coating material of the first embodiment contains a polycarboxylic acid, a polyamine compound, and a Zn compound, and (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) in the gas barrier coating material is 0.40 to 0.70.

[0082] The gas barrier coating material of the first embodiment includes a polycarboxylic acid, a polyamine compound, and a Zn compound, thereby providing a gas barrier material having improved barrier properties such as oxygen barrier properties and water vapor barrier properties before and after the retorting treatment. In addition, by making the (number of moles of Zn compound in the gas barrier coating material) / (number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) in the gas barrier coating material of the first embodiment 0.40 or more and 0.70 or less, the Zn compound is contained in an amount greater than the conventional content, thereby providing a gas barrier material having improved barrier properties even by a low-temperature short-time heat treatment compared to the conventional manufacturing method.

[0083] In the gas barrier coating material of the first embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is greater than 0.40, preferably greater than 0.41, and more preferably greater than 0.42.

[0084] From the same viewpoint, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.70 or less, preferably 0.60 or less, and more preferably 0.50 or less.

[0085] The components contained in the gas barrier coating material according to the first embodiment will be described in detail.

[0086] (Polycarboxylic Acid)

[0087] The gas barrier coating material of the first embodiment contains a polycarboxylic acid. The polycarboxylic acid contained in the gas barrier coating material of the first embodiment has two or more carboxyl groups in the molecule. Specifically, homopolymers of α,β-unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, 3-hexenedioic acid, or copolymers thereof can be cited. In addition, it can also be a copolymer formed by the above-mentioned α,β-unsaturated carboxylic acid and esters such as ethyl esters, olefins such as ethylene, etc.

[0088] Among these, preferred are homopolymers of acrylic acid, methacrylic acid, itaconic acid, fumaric acid, crotonic acid, and cinnamic acid, or copolymers thereof; more preferred are one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid; further preferred are at least one polymer selected from polyacrylic acid and polymethacrylic acid; and further preferred are at least one polymer selected from homopolymers of acrylic acid and homopolymers of methacrylic acid.

[0089] Here, in the first embodiment, polyacrylic acid includes both homopolymers of acrylic acid and copolymers of acrylic acid and other monomers. In the case of copolymers of acrylic acid and other monomers, polyacrylic acid contains, for example, 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from acrylic acid in 100% by mass of the polymer.

[0090] In the first embodiment, the polymethacrylic acid includes both a homopolymer of methacrylic acid and a copolymer of methacrylic acid and other monomers. In the case of a copolymer of methacrylic acid and other monomers, the polymethacrylic acid contains, for example, 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from methacrylic acid in 100% by mass of the polymer.

[0091] The polycarboxylic acid is a polymer obtained by polymerizing carboxylic acid monomers. From the viewpoint of excellent balance between gas barrier properties and handling properties, the molecular weight of the polycarboxylic acid is preferably 500 to 2,500,000, more preferably 5,000 to 2,000,000, more preferably 10,000 to 1,500,000, further preferably 100,000 to 1,200,000, further preferably 300,000 to 1,100,000, further preferably 500,000 to 1,000,000, further preferably 600,000 to 900,000.

[0092] Here, in the first embodiment, the molecular weight of the polycarboxylic acid is a weight average molecular weight in terms of polyethylene oxide, and can be measured using gel permeation chromatography (GPC).

[0093] At least a portion of the polycarboxylic acid can be neutralized by a volatile base. By neutralizing the polycarboxylic acid with a volatile base, gelation can be suppressed when the Zn compound, the polyamine compound and the polycarboxylic acid are mixed. Therefore, in the polycarboxylic acid, from the viewpoint of preventing gelation, it is preferred to use a volatile base to prepare a partially neutralized or completely neutralized product of the carboxyl group. The neutralized product can be obtained by partially or completely neutralizing the carboxyl group of the polycarboxylic acid with a volatile base (that is, partially or completely preparing the carboxyl group of the polycarboxylic acid into a carboxylate). Thus, gelation can be prevented when adding a polyamine compound or a Zn compound.

[0094] The partially neutralized product can be prepared by adding a volatile base to an aqueous solution of a polycarboxylic acid polymer, and a desired neutralization degree can be obtained by adjusting the amount ratio of the polycarboxylic acid to the volatile base. In the first embodiment, from the viewpoint of fully suppressing gelation caused by the neutralization reaction with the amino group of the polyamine compound, the neutralization degree of the polycarboxylic acid obtained by the volatile base is preferably 70 to 300 equivalents, more preferably 90 to 250 equivalents, and further preferably 100 to 200 equivalents.

[0095] As the volatile base, any water-soluble base can be used.

[0096] Examples of the volatile base include ammonia, morpholine, alkylamines, tertiary amines such as 2-dimethylaminoethanol, N-methylmorpholine, ethylenediamine, triethylamine, or aqueous solutions thereof, or mixtures thereof. From the viewpoint of obtaining good gas barrier properties, aqueous ammonia solutions are preferred.

[0097] (Polyamine compounds)

[0098] The gas barrier coating material of the first embodiment contains a polyamine compound. By containing a polyamine compound, the barrier properties of the obtained gas barrier material can be improved.

[0099] The polyamine compound is a compound having two or more amino groups in the main chain, side chain or terminal, and is preferably a polymer. Specifically, examples thereof include aliphatic polyamines such as polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine); polyamides having amino groups in the side chains such as polylysine and polyarginine; and the like. In addition, the polyamine may be a polyamine in which a part of the amino groups is modified.

[0100] From the viewpoint of obtaining good gas barrier properties, the polyamine compound preferably contains one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine and poly(trimethyleneimine), more preferably contains polyethyleneimine, and even more preferably polyethyleneimine.

[0101] From the viewpoint of excellent balance between gas barrier properties and handling properties, the number average molecular weight of the polyamine compound is preferably 50 to 2,000,000, more preferably 100 to 1,000,000, further preferably 1,500 to 500,000, further preferably 1,500 to 100,000, further preferably 1,500 to 50,000, further preferably 3,500 to 20,000, further preferably 5,000 to 15,000, further preferably 7,000 to 12,000.

[0102] Here, in the first embodiment, the molecular weight of the polyamine compound can be measured by a boiling point rise method or a viscosity method.

[0103] From the viewpoint of further improving the gas barrier performance after the steaming treatment, the (number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) in the gas barrier coating material of the first embodiment is preferably 0.40 or more, more preferably 0.43 or more, further preferably 0.45 or more, further preferably 0.50 or more, and further preferably 0.53 or more.

[0104] From the same viewpoint, (the number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.70 or less, more preferably 0.65 or less, further preferably 0.60 or less, and further preferably 0.58 or less.

[0105] Although the detailed reason is unclear, it is believed that by forming a dense structure with good balance between amide crosslinking (which is formed by the amino group constituting the polyamine compound) and metal crosslinking (which is formed by Zn constituting the salt of polycarboxylic acid and Zn), a gas barrier layer 103 with excellent gas barrier performance after steaming treatment and a gas barrier laminate having the same can be obtained.

[0106] (Zn compound)

[0107] The Zn compound contained in the gas barrier coating material of the first embodiment specifically includes oxides, hydroxides, halides, carbonates, phosphates, phosphites, hypophosphites, sulfates or sulfites of zinc (Zn), etc. From the viewpoint of water resistance, impurities, etc., it is at least one of zinc oxide and zinc hydroxide, and zinc oxide is more preferred.

[0108] From the viewpoint of further improving the gas barrier performance after the steaming treatment, in the gas barrier coating material of the first embodiment, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of the amino group contained in the polyamine compound in the gas barrier coating material) is preferably 0.50 or more, more preferably 0.60 or more, further preferably 0.70 or more, and further preferably 0.75 or more.

[0109] From the same viewpoint, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) is preferably 1.00 or less, more preferably 0.95 or less, and even more preferably 0.90 or less.

[0110] The gas barrier coating material according to the first embodiment may contain components other than the above-mentioned components.

[0111] For example, the gas barrier coating material of the first embodiment preferably further contains a carbonate-based ammonium salt. The carbonate-based ammonium salt is added to make the Zn compound a zinc ammonium carbonate complex, improve the solubility of the Zn compound, and prepare a uniform solution containing the Zn compound. By making the gas barrier coating material contain a carbonate-based ammonium salt, the amount of Zn compound dissolved can be increased, and as a result, the gas barrier coating material containing the Zn compound can be made more uniform.

[0112] Examples of the carbonate-based ammonium salt include ammonium carbonate and ammonium hydrogen carbonate. Ammonium carbonate is preferred because it is easily volatilized and is unlikely to remain in the obtained gas barrier layer.

[0113] From the viewpoint of further improving the solubility of the Zn compound, (the number of moles of the carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of the Zn compound in the gas barrier coating material) is preferably 0.05 or more, more preferably 0.10 or more, further preferably 0.25 or more, further preferably 0.50 or more, and further preferably 0.75 or more.

[0114] In addition, from the viewpoint of further improving the coating properties of the gas barrier coating material, (the number of moles of the carbonate ammonium salt in the gas barrier coating material) / (the number of moles of the Zn compound in the gas barrier coating material) is preferably 10.0 or less, more preferably 5.0 or less, further preferably 2.0 or less, and further preferably 1.5 or less.

[0115] (Phosphorus compound or its salt)

[0116] When the gas barrier layer of the gas barrier laminate described below was subjected to mass spectrometry analysis, PO 2- and / or PO 3- In order to provide such a gas barrier layer, the gas barrier coating material of the first embodiment preferably contains a phosphorus introduction source. As such a phosphorus introduction source, it is more preferable to contain a phosphorus compound or a salt thereof.

[0117] The phosphorus compound or the phosphorus compound in its salt contains one or more -P-OH groups in its molecular structure. The phosphorus compound may be added to the mixture in the form of a salt.

[0118] From the viewpoint of further improving the water vapor barrier property after retorting, the phosphorus compound preferably contains 2 or more -P-OH groups, and more preferably contains 3 or more -P-OH groups. In addition, from the viewpoint of productivity, the number of -P-OH groups in the phosphorus compound may be, for example, 10 or less.

[0119] Specific examples of the phosphorus compound include phosphoric acid compounds, phosphorous acid compounds, phosphonic acid compounds, hypophosphorous acid compounds, polyphosphoric acid compounds, and derivatives thereof.

[0120] Specifically, the polyphosphoric acid compound has a condensed structure of two or more phosphoric acids in its molecular structure, and examples thereof include diphosphoric acid (pyrophosphoric acid), triphosphoric acid, and polyphosphoric acid compounds in which four or more phosphoric acids are condensed.

[0121] Specific examples of the derivatives include: esters of the above-mentioned phosphorus compounds such as phosphorylated starch and phosphoric acid cross-linked starch; halides such as chlorides; anhydrides such as tetraphosphorus decoxide; and compounds having a structure in which the hydrogen atom bonded to the phosphorus atom is substituted with an alkyl group, such as nitrilotris(methylenephosphonic acid) and N,N,N',N'-ethylenediaminetetrakis(methylenephosphonic acid).

[0122] From the viewpoint of further improving the balance between barrier properties and productivity, the phosphorus compound is one or more selected from the group consisting of phosphoric acid compounds, phosphorous acid compounds, hypophosphorous acid compounds, polyphosphoric acid compounds, phosphonic acid compounds and their salts, and more preferably at least one selected from the group consisting of phosphoric acid compounds, phosphorous acid compounds, phosphonic acid compounds and their salts.

[0123] Specific examples of the salt in the salt of the phosphorus compound include salts of monovalent metals such as sodium and potassium; and ammonium salts. From the viewpoint of barrier properties, the salt of the phosphorus compound is preferably an ammonium salt.

[0124] As a specific example of such a compound, for example, diammonium hydrogen phosphate can be mentioned.

[0125] (polyphosphate compound or its salt)

[0126] Among the above-mentioned phosphorus compounds or salts thereof, polyphosphoric acid compounds or salts thereof are preferred as the phosphorus introduction source from the viewpoint of improving the above-mentioned productivity and barrier properties and being able to impart water resistance.

[0127] Specific examples of the salt in the salt of the polyphosphate compound include salts of monovalent metals such as sodium and potassium; and ammonium salts. From the viewpoint of barrier properties, the salt of the polyphosphate compound is preferably an ammonium salt.

[0128] As specific examples of polyphosphate compounds or their salts, preferably at least one selected from the group consisting of oligopolyphosphoric acid, ammonium oligopolyphosphate, sodium oligopolyphosphate, potassium oligopolyphosphate and the like, or their salts; pyrophosphoric acid, ammonium pyrophosphate, sodium pyrophosphate, potassium pyrophosphate and the like, or their salts; tripolyphosphoric acid, ammonium tripolyphosphate, sodium tripolyphosphate, potassium tripolyphosphate and the like, or their salts; and tetrapolyphosphoric acid, ammonium tetrapolyphosphate, sodium tetrapolyphosphate, potassium tetrapolyphosphate and the like, or their salts. Among these, from the viewpoint of further improving the balance between the barrier properties and the pot life of the gas barrier coating material, oligopolyphosphoric acid or its salt is preferred, and ammonium oligopolyphosphate is more preferred. Here, in the present specification, "oligopolyphosphoric acid" refers to, for example, a polyphosphoric acid having a degree of polymerization of 5 or more and 100 or less.

[0129] In the first embodiment, from the viewpoint of improving barrier properties, (the number of moles of P contained in the phosphorus compound or its salt in the gas barrier coating material) / (the number of moles of COO- groups contained in the polycarboxylic acid in the gas barrier coating material) or (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.005 or more, more preferably 0.007 or more, and further preferably 0.010 or more. In a phosphorus compound such as phosphoric acid containing one P atom in the chemical formula, the number of moles of P atoms has the same meaning as the number of moles of the phosphorus compound. In addition, in a phosphorus compound and a polyphosphate compound containing a plurality of P atoms in the chemical formula, the number obtained by multiplying the number of P atoms contained in the chemical formula by the number of moles of the phosphorus compound and the polyphosphate compound becomes the number of moles of P atoms.

[0130] In addition, from the viewpoint of barrier properties and productivity, (the number of moles of P contained in the phosphorus compound or its salt in the gas barrier coating material) / (the number of moles of COO- groups contained in the polycarboxylic acid in the gas barrier coating material) or (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.20 or less, more preferably 0.15 or less, further preferably 0.12 or less, and further preferably 0.10 or less.

[0131] (Surfactant)

[0132] Furthermore, from the viewpoint of improving the above-mentioned productivity and barrier properties and suppressing the generation of depressions when applied as a gas barrier coating material, the gas barrier coating material of the first embodiment preferably further contains a surfactant.

[0133] When the solid content of the gas barrier coating material as a whole (the total amount of components remaining as solids when the solidified material is formed) is set to 100% by mass, the content of the surfactant is preferably 0.01 to 3% by mass, and more preferably 0.01 to 1% by mass. In this specification, the solid content of the gas barrier coating material refers to the components remaining as solids when the gas barrier coating material is cured.

[0134] Examples of the surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. From the viewpoint of obtaining good coating properties, nonionic surfactants are preferred, polyoxyalkylene alkyl ethers are more preferred, and polyoxyethylene alkyl ethers are still more preferred.

[0135] Examples of the nonionic surfactant include polyoxyalkylene alkyl aryl ethers, polyoxyalkylene alkyl ethers, polyoxyalkylene fatty acid esters, sorbitan fatty acid esters, silicone-based surfactants, acetylene alcohol-based surfactants, and fluorine-containing surfactants.

[0136] Examples of the polyoxyalkylene alkyl aryl ethers include polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene dodecylphenyl ether, and the like.

[0137] Examples of the polyoxyalkylene alkyl ethers include polyoxyethylene alkyl ethers such as polyoxyethylene oleyl ether and polyoxyethylene lauryl ether.

[0138] Examples of the polyoxyalkylene fatty acid esters include polyoxyethylene oleate, polyoxyethylene laurate, polyoxyethylene distearate, and the like.

[0139] Examples of the sorbitan fatty acid esters include sorbitan laurate, sorbitan monostearate, sorbitan monooleate, sorbitan sesquioleate, polyoxyethylene monooleate, and polyoxyethylene stearate.

[0140] Examples of the silicone-based surfactant include dimethylpolysiloxane and the like.

[0141] Examples of the acetylene alcohol surfactant include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,6-dimethyl-4-octyne-3,6-diol, and 3,5-dimethyl-1-hexyne-3-ol.

[0142] Examples of the fluorine-containing surfactant include fluoroalkyl esters and the like.

[0143] (Crosslinking agent)

[0144] From the viewpoint of improving the above-mentioned productivity and barrier properties and improving the alkali resistance to alkaline liquids (for example, alkaline detergents, etc.), the gas barrier coating material of the first embodiment preferably further contains a crosslinking agent.

[0145] As such a crosslinking agent, a known crosslinking agent can be used, preferably comprising one or more compounds selected from the group consisting of epoxy silane compounds, carbodiimide compounds and isocyanate compounds, more preferably comprising one or more compounds selected from the group consisting of epoxy silane compounds and carbodiimide compounds.

[0146] In the gas barrier coating material of the first embodiment, when the solid content of the gas barrier coating material as a whole is set to 100% by mass, the content of the crosslinking agent is preferably 0.010% by mass or more, and more preferably 0.015% by mass or more. By making the content of the crosslinking agent equal to or greater than the above lower limit, the alkali resistance of the gas barrier layer formed by the gas barrier coating material of the first embodiment becomes more suitable.

[0147] The content of the crosslinking agent is preferably 2% by mass or less, more preferably 1% by mass or less, and further preferably 0.05% by mass or less. By setting the content of the crosslinking agent to be below the upper limit, the productivity and barrier properties of the gas barrier coating material of the first embodiment are more suitable.

[0148] The gas barrier coating material of the first embodiment may contain additives other than the above-mentioned components, for example, various additives such as lubricants, slip agents, anti-blocking agents, antistatic agents, anti-fogging agents, pigments, dyes, and inorganic or organic fillers may be added.

[0149] In addition, from the viewpoint of improving coating properties when applied as a gas barrier coating material, the solid content concentration of the gas barrier coating material of the first embodiment is preferably 0.5 to 15% by mass, more preferably 1 to 10% by mass, further preferably 1 to 5% by mass, and further preferably 1 to 3% by mass.

[0150] <Second Embodiment>

[0151] The gas barrier coating material of the second embodiment is a gas barrier coating material comprising a polycarboxylic acid, a polyamine compound, and a Zn compound. For the cured product of the gas barrier coating material, the Zn composition ratio measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output power: 15 kV, 10 mA is 3.0 atomic% or more and 10.0 atomic% or less.

[0152] Here, the cured product of the gas barrier coating material can be obtained, for example, by coating the gas barrier coating material on a biaxially stretched polyethylene terephthalate film so that the coating amount after drying becomes 0.3 μm, and then heat treating the film at 130° C. for 60 seconds.

[0153] The gas barrier coating material of the second embodiment includes a polycarboxylic acid, a polyamine compound, and a Zn compound, thereby providing a gas barrier material having improved barrier properties such as oxygen barrier property and water vapor barrier property before and after retorting. Furthermore, the composition ratio of Zn measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output power: 15 kV, 10 mA is 3.0 atomic% or more and 10.0 atomic% or less, thereby improving the barrier property and the peel strength of the gas barrier material.

[0154] In the gas barrier coating material of the second embodiment, for the cured product obtained by curing the gas barrier coating material, the composition ratio of Zn measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output power: 15 kV, 10 mA is 3.0 atomic% or more, preferably 3.5 atomic% or more, and more preferably 3.7 atomic% or more. By making the composition ratio of Zn equal to or greater than the above lower limit, the barrier properties and the peel strength of the gas barrier material can be further improved.

[0155] The composition ratio of Zn is 10.0 atomic % or less, more preferably 9.0 atomic % or less, further preferably 8.0 atomic % or less, further preferably 7.0 atomic % or less, further preferably 6.0 atomic % or less.

[0156] By setting the composition ratio of Zn to be equal to or less than the above upper limit, the barrier properties and the peel strength of the gas barrier material can be further improved.

[0157] An example of specific conditions of the above-mentioned X-ray photoelectron spectroscopy analysis is shown.

[0158] Analyzer: AXIS-NOVA manufactured by KRATOS

[0159] X-ray source: monochromatized Al-Kα

[0160] X-ray source output power: 15kV, 10mA

[0161] Analysis area: 300×700μm

[0162] A neutralizing electron gun is used for charge correction during analysis.

[0163] In order to analyze the interior of the cured gas barrier coating material, it is desirable to sputter-etch the surface of the cured gas barrier coating material before analysis. Among them, in order to reduce the damage to the cured gas barrier coating material caused by etching, etching based on an Ar-gas cluster ion beam source is desirable.

[0164] The detection element is determined by wide scanning, and the spectrum of each element is obtained by narrow scanning. Then, the background calculated by Shirley method is removed from the obtained spectrum, and the atomic composition ratio (atomic %) of the detection element is calculated based on the obtained peak area using the relative sensitivity coefficient method.

[0165] The components contained in the gas barrier coating material according to the second embodiment will be described in detail.

[0166] (Polycarboxylic Acid)

[0167] The gas barrier coating material of the second embodiment contains a polycarboxylic acid. The polycarboxylic acid contained in the gas barrier coating material of the second embodiment has two or more carboxyl groups in the molecule. Specifically, homopolymers of α,β-unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, 3-hexenedioic acid, or their copolymers can be cited. In addition, it can also be a copolymer formed by the above-mentioned α,β-unsaturated carboxylic acid and esters such as ethyl esters, olefins such as ethylene, etc.

[0168] Among these, one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid are preferred, at least one polymer selected from polyacrylic acid and polymethacrylic acid is more preferred, and at least one polymer selected from homopolymers of acrylic acid and homopolymers of methacrylic acid is further preferred.

[0169] Here, in the second embodiment, polyacrylic acid includes both homopolymers of acrylic acid and copolymers of acrylic acid and other monomers. In the case of copolymers of acrylic acid and other monomers, polyacrylic acid contains, for example, 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from acrylic acid in 100% by mass of the polymer.

[0170] In the second embodiment, the polymethacrylic acid includes both a homopolymer of methacrylic acid and a copolymer of methacrylic acid and other monomers. In the case of a copolymer of methacrylic acid and other monomers, the polymethacrylic acid contains, for example, 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from methacrylic acid in 100% by mass of the polymer.

[0171] The polycarboxylic acid is a polymer obtained by polymerizing carboxylic acid monomers. From the viewpoint of excellent balance between gas barrier properties and handling properties, the molecular weight of the polycarboxylic acid is preferably 500 to 2,500,000, more preferably 5,000 to 2,000,000, more preferably 10,000 to 1,500,000, further preferably 100,000 to 1,200,000, further preferably 300,000 to 1,100,000, further preferably 500,000 to 1,000,000, further preferably 600,000 to 900,000.

[0172] Here, in the second embodiment, the molecular weight of the polycarboxylic acid is a weight average molecular weight in terms of polyethylene oxide, and can be measured using gel permeation chromatography (GPC).

[0173] At least a portion of the polycarboxylic acid can be neutralized by a volatile base. By neutralizing the polycarboxylic acid with a volatile base, gelation can be suppressed when the Zn compound, the polyamine compound and the polycarboxylic acid are mixed. Therefore, in the polycarboxylic acid, from the viewpoint of preventing gelation, it is preferred to use a volatile base to prepare a partially neutralized or completely neutralized product of the carboxyl group. The neutralized product can be obtained by partially or completely neutralizing the carboxyl group of the polycarboxylic acid with a volatile base (that is, partially or completely preparing the carboxyl group of the polycarboxylic acid into a carboxylate). Thus, gelation can be prevented when adding a polyamine compound or a Zn compound.

[0174] The partially neutralized product can be prepared by adding a volatile base to an aqueous solution of a polycarboxylic acid polymer, and a desired neutralization degree can be obtained by adjusting the amount ratio of the polycarboxylic acid to the volatile base. In the second embodiment, from the viewpoint of fully suppressing gelation caused by the neutralization reaction with the amino group of the polyamine compound, the neutralization degree of the polycarboxylic acid obtained by the volatile base is preferably 70 to 300 equivalents, more preferably 90 to 250 equivalents, and further preferably 100 to 200 equivalents.

[0175] As the volatile base, any water-soluble base can be used.

[0176] Examples of the volatile base include ammonia, morpholine, alkylamines, tertiary amines such as 2-dimethylaminoethanol, N-methylmorpholine, ethylenediamine, triethylamine, or aqueous solutions thereof, or mixtures thereof. From the viewpoint of obtaining good gas barrier properties, aqueous ammonia solutions are preferred.

[0177] (Polyamine compounds)

[0178] The gas barrier coating material of the second embodiment contains a polyamine compound. By containing a polyamine compound, the barrier properties of the obtained gas barrier material can be improved.

[0179] The polyamine compound is a compound having two or more amino groups in the main chain, side chain or terminal, and is preferably a polymer. Specifically, examples thereof include aliphatic polyamines such as polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine); polyamides having amino groups in the side chains such as polylysine and polyarginine; and the like. In addition, the polyamine may be a polyamine in which a part of the amino groups is modified.

[0180] From the viewpoint of obtaining good gas barrier properties, the polyamine compound preferably contains one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine and poly(trimethyleneimine), more preferably contains polyethyleneimine, and even more preferably polyethyleneimine.

[0181] From the viewpoint of excellent balance between gas barrier properties and handling properties, the number average molecular weight of the polyamine compound is preferably 50 to 2,000,000, more preferably 100 to 1,000,000, further preferably 1,500 to 500,000, further preferably 1,500 to 100,000, further preferably 1,500 to 50,000, further preferably 3,500 to 20,000, further preferably 5,000 to 15,000, further preferably 7,000 to 12,000.

[0182] Here, in the second embodiment, the molecular weight of the polyamine compound can be measured by a boiling point rise method or a viscosity method.

[0183] From the viewpoint of further improving the gas barrier performance after the steaming treatment, the (number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) in the gas barrier coating material of the second embodiment is preferably 0.40 or more, more preferably 0.43 or more, further preferably 0.45 or more, further preferably 0.50 or more, and further preferably 0.53 or more.

[0184] From the same viewpoint, (the number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.70 or less, more preferably 0.65 or less, further preferably 0.60 or less, and further preferably 0.58 or less.

[0185] Although the detailed reason is unclear, it is believed that by forming a dense structure with good balance between amide crosslinking (which is formed by the amino group constituting the polyamine compound) and metal crosslinking (which is formed by Zn constituting the salt of polycarboxylic acid and Zn), a gas barrier layer 103 with excellent gas barrier performance after steaming treatment and a gas barrier laminate having the same can be obtained.

[0186] (Zn compound)

[0187] The gas barrier coating material of the second embodiment includes a Zn compound. Specifically, the Zn compound includes oxides, hydroxides, halides, carbonates, phosphates, phosphites, hypophosphites, sulfates or sulfites of zinc (Zn). From the viewpoint of water resistance, impurities, etc., at least one of zinc oxide and zinc hydroxide is preferred, and zinc oxide is more preferred.

[0188] In the gas barrier coating material of the second embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.40 or more, preferably 0.41 or more, and more preferably 0.42 or more.

[0189] From the same viewpoint, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.70 or less, preferably 0.60 or less, and more preferably 0.50 or less.

[0190] In the second embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of the amino group contained in the polyamine compound in the gas barrier coating material) is preferably 0.50 or more, more preferably 0.60 or more, further preferably 0.70 or more, and further preferably 0.75 or more.

[0191] From the same viewpoint, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) is preferably 1.00 or less, more preferably 0.95 or less, and even more preferably 0.90 or less.

[0192] The gas barrier coating material according to the second embodiment may contain components other than the above-mentioned components.

[0193] For example, the gas barrier coating material of the second embodiment preferably further contains a carbonate-based ammonium salt. The carbonate-based ammonium salt is added to make the Zn compound a zinc ammonium carbonate complex, improve the solubility of the Zn compound, and prepare a uniform solution containing the Zn compound. By making the gas barrier coating material contain a carbonate-based ammonium salt, the amount of Zn compound dissolved can be increased, and as a result, the gas barrier coating material containing the Zn compound can be made more uniform.

[0194] Examples of the carbonate-based ammonium salt include ammonium carbonate and ammonium hydrogen carbonate. Ammonium carbonate is preferred because it is easily volatilized and is unlikely to remain in the obtained gas barrier layer.

[0195] From the viewpoint of further improving the solubility of the Zn compound, (the number of moles of the carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of the Zn compound in the gas barrier coating material) is preferably 0.05 or more, more preferably 0.10 or more, further preferably 0.25 or more, further preferably 0.50 or more, and further preferably 0.75 or more.

[0196] In addition, from the viewpoint of further improving the coating properties of the gas barrier coating material, (the number of moles of the carbonate ammonium salt in the gas barrier coating material) / (the number of moles of the Zn compound in the gas barrier coating material) is preferably 10.0 or less, more preferably 5.0 or less, further preferably 2.0 or less, and further preferably 1.5 or less.

[0197] (polyphosphate compound or its salt)

[0198] The gas barrier coating material of the second embodiment preferably contains a polyphosphoric acid compound or a salt thereof. This can improve the gas barrier properties and the water resistance of the gas barrier coating material, and as a result, can further improve the peel strength.

[0199] Specifically, the polyphosphoric acid compound has a condensed structure of two or more phosphoric acids in its molecular structure, and examples thereof include diphosphoric acid (pyrophosphoric acid), triphosphoric acid (tripolyphosphoric acid), and polyphosphoric acid compounds in which four or more phosphoric acids are condensed.

[0200] Specific examples of the salt in the salt of the polyphosphate compound include salts of monovalent metals such as sodium and potassium; and ammonium salts. From the viewpoint of barrier properties, the salt of the polyphosphate compound is preferably an ammonium salt.

[0201] As specific examples of polyphosphate compounds or their salts, preferably at least one selected from the group consisting of oligopolyphosphoric acid, ammonium oligopolyphosphate, sodium oligopolyphosphate, potassium oligopolyphosphate and the like, or their salts; pyrophosphoric acid, ammonium pyrophosphate, sodium pyrophosphate, potassium pyrophosphate and the like, or their salts; tripolyphosphoric acid, ammonium tripolyphosphate, sodium tripolyphosphate, potassium tripolyphosphate and the like, or their salts; and tetrapolyphosphoric acid, ammonium tetrapolyphosphate, sodium tetrapolyphosphate, potassium tetrapolyphosphate and the like, or their salts. Among these, from the viewpoint of further improving the balance between the barrier properties and the pot life of the gas barrier coating material, oligopolyphosphoric acid or its salt is preferred, and ammonium oligopolyphosphate is more preferred. Here, in the present specification, "oligopolyphosphoric acid" refers to, for example, a polyphosphoric acid having a degree of polymerization of 5 or more and 100 or less.

[0202] In the second embodiment, from the viewpoint of improving barrier properties, (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.005 or more, more preferably 0.007 or more, and further preferably 0.010 or more. In a polyphosphate compound containing a plurality of P atoms in the chemical formula, the number obtained by multiplying the number of P atoms contained in the chemical formula by the number of moles of the polyphosphate compound becomes the number of moles of P atoms.

[0203] In addition, from the viewpoint of barrier properties and peel strength, (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.20 or less, more preferably 0.15 or less, and further preferably 0.10 or less.

[0204] (Surfactant)

[0205] In addition, from the viewpoint of improving the above-mentioned barrier properties and peel strength and suppressing the generation of depressions when applied as a gas barrier coating material, the gas barrier coating material of the second embodiment preferably further contains a surfactant.

[0206] When the solid content of the gas barrier coating material as a whole (the total amount of components remaining as solids when the solidified material is formed) is set to 100% by mass, the content of the surfactant is preferably 0.01 to 3% by mass, and more preferably 0.01 to 1% by mass. In this specification, the solid content of the gas barrier coating material refers to the components remaining as solids when the gas barrier coating material is cured.

[0207] Examples of the surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. From the viewpoint of obtaining good coating properties, nonionic surfactants are preferred, polyoxyalkylene alkyl ethers are more preferred, and polyoxyethylene alkyl ethers are further preferred.

[0208] Examples of the nonionic surfactant include polyoxyalkylene alkyl aryl ethers, polyoxyalkylene alkyl ethers, polyoxyalkylene fatty acid esters, sorbitan fatty acid esters, silicone-based surfactants, acetylene alcohol-based surfactants, and fluorine-containing surfactants.

[0209] Examples of the polyoxyalkylene alkyl aryl ethers include polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene dodecylphenyl ether, and the like.

[0210] Examples of the polyoxyalkylene alkyl ethers include polyoxyethylene alkyl ethers such as polyoxyethylene oleyl ether and polyoxyethylene lauryl ether.

[0211] Examples of the polyoxyalkylene fatty acid esters include polyoxyethylene oleate, polyoxyethylene laurate, polyoxyethylene distearate, and the like.

[0212] Examples of the sorbitan fatty acid esters include sorbitan laurate, sorbitan monostearate, sorbitan monooleate, sorbitan sesquioleate, polyoxyethylene monooleate, and polyoxyethylene stearate.

[0213] Examples of the silicone-based surfactant include dimethylpolysiloxane and the like.

[0214] Examples of the acetylene alcohol surfactant include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,6-dimethyl-4-octyne-3,6-diol, and 3,5-dimethyl-1-hexyne-3-ol.

[0215] Examples of the fluorine-containing surfactant include fluoroalkyl esters and the like.

[0216] (Crosslinking agent)

[0217] From the viewpoint of improving the above-mentioned barrier properties and peel strength and improving the alkali resistance to alkaline liquids (for example, alkaline detergents, etc.), the gas barrier coating material of the second embodiment preferably further contains a crosslinking agent.

[0218] As such a crosslinking agent, a known crosslinking agent can be used, preferably comprising one or more compounds selected from the group consisting of epoxy silane compounds, carbodiimide compounds and isocyanate compounds, more preferably comprising one or more compounds selected from the group consisting of epoxy silane compounds and carbodiimide compounds.

[0219] In the gas barrier coating material of the second embodiment, when the solid content of the gas barrier coating material as a whole is set to 100% by mass, the content of the crosslinking agent is preferably 0.010% by mass or more, and more preferably 0.015% by mass or more. By making the content of the crosslinking agent equal to or more than the above lower limit, the alkali resistance of the gas barrier layer formed by the gas barrier coating material of the second embodiment becomes more suitable.

[0220] The content of the crosslinking agent is preferably 2% by mass or less, more preferably 1% by mass or less, and further preferably 0.05% by mass or less. By setting the content of the crosslinking agent to be below the upper limit, the productivity and barrier properties of the gas barrier coating material of the second embodiment become more suitable.

[0221] The gas barrier coating material of the second embodiment may contain additives other than the above-mentioned components, for example, various additives such as lubricants, slip agents, anti-blocking agents, antistatic agents, anti-fogging agents, pigments, dyes, and inorganic or organic fillers may be added.

[0222] In addition, from the viewpoint of improving coating properties when applied as a gas barrier coating material, the solid content concentration of the gas barrier coating material of the second embodiment is preferably 0.5 to 15% by mass, more preferably 1 to 10% by mass, further preferably 1 to 5% by mass, and further preferably 1 to 3% by mass.

[0223] (physical properties)

[0224] In the gas barrier coating material of the second embodiment, for the cured product obtained by curing the gas barrier coating material, the P composition ratio measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA is preferably 0.05 atomic% or more, more preferably 0.10 atomic% or more, and further preferably 0.20 atomic% or more. By making the P composition ratio equal to or greater than the above lower limit, the barrier properties can be further improved.

[0225] The composition ratio of P is preferably 1.5 atomic % or less, more preferably 1.3 atomic % or less, further preferably 1.0 atomic % or less, and further preferably 0.8 atomic % or less.

[0226] By setting the composition ratio of P to be equal to or less than the above upper limit, the reaction with Zn in the gas barrier coating material can be suppressed, and the pot life of the gas barrier coating material can be further improved.

[0227] Here, the cured product of the gas barrier coating material can be obtained, for example, by coating the gas barrier coating material on a biaxially stretched polyethylene terephthalate film so that the coating thickness after drying becomes 0.3 μm, and then heat treating the film at 130° C. for 60 seconds.

[0228] In addition, the specific conditions of the above X-ray photoelectron spectroscopy analysis are as described above.

[0229] <Third Embodiment>

[0230] The gas barrier coating material according to the third embodiment contains a polycarboxylic acid, a polyamine compound, a Zn compound, and a polyphosphoric acid compound or a salt thereof.

[0231] The gas barrier coating material of the third embodiment includes a polycarboxylic acid, a polyamine compound, a Zn compound, and a polyphosphoric acid compound or a salt thereof, thereby providing a gas barrier material having improved barrier properties such as oxygen barrier properties and water vapor barrier properties before and after retorting. In particular, by using a polyphosphoric acid compound or a salt thereof in addition to a polycarboxylic acid, a polyamine compound, and a Zn compound, the barrier properties can be improved and the pot life of the gas barrier coating material can be increased.

[0232] Components contained in the gas barrier coating material according to the third embodiment will be described in detail.

[0233] (Polycarboxylic Acid)

[0234] The gas barrier coating material of the third embodiment contains a polycarboxylic acid. The polycarboxylic acid contained in the gas barrier coating material of the third embodiment has two or more carboxyl groups in the molecule. Specifically, homopolymers of α,β-unsaturated carboxylic acids such as (meth)acrylic acid, itaconic acid, fumaric acid, crotonic acid, cinnamic acid, 3-hexenoic acid, 3-hexenedioic acid, or copolymers thereof can be cited. In addition, it can also be a copolymer formed by the above-mentioned α,β-unsaturated carboxylic acid and esters such as ethyl esters, olefins such as ethylene, etc.

[0235] Among these, preferred are homopolymers of acrylic acid, methacrylic acid, itaconic acid, fumaric acid, crotonic acid, and cinnamic acid, or copolymers thereof; more preferred are one or more polymers selected from the group consisting of polyacrylic acid, polymethacrylic acid, and copolymers of acrylic acid and methacrylic acid; more preferred are at least one polymer selected from polyacrylic acid and polymethacrylic acid; and even more preferred are at least one polymer selected from homopolymers of acrylic acid and homopolymers of methacrylic acid.

[0236] Here, in the third embodiment, the polyacrylic acid includes both a homopolymer of acrylic acid and a copolymer of acrylic acid and other monomers. In the case of a copolymer of acrylic acid and other monomers, the polyacrylic acid contains, for example, 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of a structural unit derived from acrylic acid in 100% by mass of the polymer.

[0237] In the third embodiment, the polymethacrylic acid includes both a homopolymer of methacrylic acid and a copolymer of methacrylic acid and other monomers. In the case of a copolymer of methacrylic acid and other monomers, the polymethacrylic acid includes, for example, 90% by mass or more, preferably 95% by mass or more, and more preferably 99% by mass or more of structural units derived from methacrylic acid in 100% by mass of the polymer.

[0238] The polycarboxylic acid is a polymer obtained by polymerizing carboxylic acid monomers. From the viewpoint of excellent balance between gas barrier properties and handling properties, the molecular weight of the polycarboxylic acid is preferably 500 to 2,500,000, more preferably 5,000 to 2,000,000, more preferably 10,000 to 1,500,000, further preferably 100,000 to 1,200,000, further preferably 300,000 to 1,100,000, further preferably 500,000 to 1,000,000, further preferably 600,000 to 900,000.

[0239] Here, in the third embodiment, the molecular weight of the polycarboxylic acid is a weight average molecular weight in terms of polyethylene oxide, and can be measured using gel permeation chromatography (GPC).

[0240] At least a portion of the polycarboxylic acid can be neutralized by a volatile base. By neutralizing the polycarboxylic acid with a volatile base, gelation can be suppressed when the Zn compound, the polyamine compound and the polycarboxylic acid are mixed. Therefore, in the polycarboxylic acid, from the viewpoint of preventing gelation, it is preferred to use a volatile base to prepare a partially neutralized or completely neutralized product of the carboxyl group. The neutralized product can be obtained by partially or completely neutralizing the carboxyl group of the polycarboxylic acid with a volatile base (that is, partially or completely preparing the carboxyl group of the polycarboxylic acid into a carboxylate). Thus, gelation can be prevented when adding a polyamine compound or a Zn compound.

[0241] The partially neutralized product can be prepared by adding a volatile base to an aqueous solution of a polycarboxylic acid polymer, and a desired neutralization degree can be obtained by adjusting the amount ratio of the polycarboxylic acid to the volatile base. In the third embodiment, from the viewpoint of fully suppressing gelation caused by the neutralization reaction with the amino group of the polyamine compound, the neutralization degree of the polycarboxylic acid obtained by the volatile base is preferably 70 to 300 equivalents, more preferably 90 to 250 equivalents, and further preferably 100 to 200 equivalents.

[0242] As the volatile base, any water-soluble base can be used.

[0243] Examples of the volatile base include ammonia, morpholine, alkylamines, tertiary amines such as 2-dimethylaminoethanol, N-methylmorpholine, ethylenediamine, triethylamine, or aqueous solutions thereof, or mixtures thereof. From the viewpoint of obtaining good gas barrier properties, aqueous ammonia solutions are preferred.

[0244] (Polyamine compounds)

[0245] The gas barrier coating material of the third embodiment contains a polyamine compound. By containing a polyamine compound, the barrier properties of the obtained gas barrier material can be improved.

[0246] The polyamine compound is a compound having two or more amino groups in the main chain, side chain or terminal, and is preferably a polymer. Specifically, examples thereof include aliphatic polyamines such as polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine); polyamides having amino groups in the side chains such as polylysine and polyarginine; and the like. In addition, polyamines in which a part of the amino groups is modified may also be used.

[0247] From the viewpoint of obtaining good gas barrier properties, the polyamine compound preferably contains one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine and poly(trimethyleneimine), more preferably contains polyethyleneimine, and even more preferably polyethyleneimine.

[0248] From the viewpoint of excellent balance between gas barrier properties and handling properties, the number average molecular weight of the polyamine compound is preferably 50 to 2,000,000, more preferably 100 to 1,000,000, further preferably 1,500 to 500,000, further preferably 1,500 to 100,000, further preferably 1,500 to 50,000, further preferably 3,500 to 20,000, further preferably 5,000 to 15,000, further preferably 7,000 to 12,000.

[0249] Here, in the third embodiment, the molecular weight of the polyamine compound can be measured by a boiling point rise method or a viscosity method.

[0250] From the viewpoint of further improving the gas barrier performance after the steaming treatment, the (number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) in the gas barrier coating material of the third embodiment is preferably 0.40 or more, more preferably 0.43 or more, further preferably 0.45 or more, further preferably 0.50 or more, and further preferably 0.53 or more.

[0251] From the same viewpoint, (the number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.70 or less, more preferably 0.65 or less, further preferably 0.60 or less, and further preferably 0.58 or less.

[0252] Although the detailed reason is unclear, it is believed that by forming a dense structure with good balance between amide crosslinking (which is formed by the amino group constituting the polyamine compound) and metal crosslinking (which is formed by Zn constituting the salt of polycarboxylic acid and Zn), a gas barrier layer 103 with excellent gas barrier performance after steaming treatment and a gas barrier laminate having the same can be obtained.

[0253] (Zn compound)

[0254] The gas barrier coating material of the third embodiment includes a Zn compound. Specifically, the Zn compound includes oxides, hydroxides, halides, carbonates, phosphates, phosphites, hypophosphites, sulfates, or sulfites of zinc (Zn). From the viewpoint of water resistance, impurities, etc., at least one of zinc oxide and zinc hydroxide is preferred, and zinc oxide is more preferred.

[0255] From the viewpoint of further improving the gas barrier performance after the steaming treatment, the (number of moles of Zn compounds in the gas barrier coating material) / (number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) in the gas barrier coating material of the third embodiment is preferably 0.40 or more, preferably 0.41 or more, and more preferably 0.42 or more.

[0256] From the same viewpoint, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.70 or less, preferably 0.60 or less, and more preferably 0.50 or less.

[0257] In the third embodiment, from the viewpoint of further improving the gas barrier performance after the steaming treatment, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of the amino group contained in the polyamine compound in the gas barrier coating material) is preferably 0.50 or more, more preferably 0.60 or more, further preferably 0.70 or more, and further preferably 0.75 or more.

[0258] From the same viewpoint, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) is preferably 1.00 or less, more preferably 0.95 or less, and even more preferably 0.90 or less.

[0259] (polyphosphate compound or its salt)

[0260] The gas barrier coating material of the third embodiment contains a polyphosphoric acid compound or a salt thereof. This can improve the gas barrier properties and increase the pot life of the gas barrier coating material.

[0261] Specifically, the polyphosphoric acid compound has a condensed structure of two or more phosphoric acids in its molecular structure, and examples thereof include diphosphoric acid (pyrophosphoric acid), triphosphoric acid (tripolyphosphoric acid), and polyphosphoric acid compounds in which four or more phosphoric acids are condensed.

[0262] Specific examples of the salt in the salt of the polyphosphate compound include salts of monovalent metals such as sodium and potassium; and ammonium salts. From the viewpoint of barrier properties, the salt of the polyphosphate compound is preferably an ammonium salt.

[0263] As specific examples of polyphosphate compounds or their salts, preferably at least one selected from the group consisting of oligopolyphosphoric acid, ammonium oligopolyphosphate, sodium oligopolyphosphate, potassium oligopolyphosphate and the like, or their salts; pyrophosphoric acid, ammonium pyrophosphate, sodium pyrophosphate, potassium pyrophosphate and the like, or their salts; tripolyphosphoric acid, ammonium tripolyphosphate, sodium tripolyphosphate, potassium tripolyphosphate and the like, or their salts; and tetrapolyphosphoric acid, ammonium tetrapolyphosphate, sodium tetrapolyphosphate, potassium tetrapolyphosphate and the like, or their salts. Among these, from the viewpoint of further improving the balance between the barrier properties and the pot life of the gas barrier coating material, oligopolyphosphoric acid or its salt is preferred, and ammonium oligopolyphosphate is more preferred. Here, in the present specification, "oligopolyphosphoric acid" refers to, for example, a polyphosphorus having a degree of polymerization of 5 or more and 100 or less.

[0264] In the third embodiment, from the viewpoint of improving barrier properties, (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.005 or more, more preferably 0.007 or more, and further preferably 0.010 or more. In a polyphosphate compound containing a plurality of P atoms in the chemical formula, the number obtained by multiplying the number of P atoms contained in the chemical formula by the number of moles of the polyphosphate compound becomes the number of moles of P atoms.

[0265] In addition, from the viewpoint of barrier properties and pot life, (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is preferably 0.20 or less, more preferably 0.15 or less, further preferably 0.12 or less, and further preferably 0.10 or less.

[0266] The gas barrier coating material according to the third embodiment may contain components other than the above-mentioned components.

[0267] For example, the gas barrier coating material of the third embodiment preferably further contains a carbonate-based ammonium salt. The carbonate-based ammonium salt is added to make the Zn compound a zinc ammonium carbonate complex, improve the solubility of the Zn compound, and prepare a uniform solution containing the Zn compound. By making the gas barrier coating material contain a carbonate-based ammonium salt, the amount of the Zn compound dissolved can be increased, and as a result, the gas barrier coating material containing the Zn compound can be made more uniform.

[0268] Examples of the carbonate-based ammonium salt include ammonium carbonate and ammonium hydrogen carbonate. Ammonium carbonate is preferred because it is easily volatilized and is unlikely to remain in the obtained gas barrier layer.

[0269] From the viewpoint of further improving the solubility of the Zn compound, (the number of moles of the carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of the Zn compound in the gas barrier coating material) is preferably 0.05 or more, more preferably 0.10 or more, further preferably 0.25 or more, further preferably 0.50 or more, and further preferably 0.75 or more.

[0270] In addition, from the viewpoint of further improving the coating properties of the gas barrier coating material, (the number of moles of the carbonate ammonium salt in the gas barrier coating material) / (the number of moles of the Zn compound in the gas barrier coating material) is preferably 10.0 or less, more preferably 5.0 or less, further preferably 2.0 or less, and further preferably 1.5 or less.

[0271] (Surfactant)

[0272] Furthermore, from the viewpoint of improving the above-mentioned barrier properties and pot life and suppressing the generation of depressions when applied as a gas barrier coating material, the gas barrier coating material of the third embodiment preferably further contains a surfactant.

[0273] When the solid content of the gas barrier coating material as a whole (the total amount of components remaining as solids when the solidified material is formed) is set to 100% by mass, the content of the surfactant is preferably 0.01 to 3% by mass, and more preferably 0.01 to 1% by mass. In this specification, the solid content of the gas barrier coating material refers to the components remaining as solids when the gas barrier coating material is cured.

[0274] Examples of the surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, and amphoteric surfactants. From the viewpoint of obtaining good coating properties, nonionic surfactants are preferred, polyoxyalkylene alkyl ethers are more preferred, and polyoxyethylene alkyl ethers are still more preferred.

[0275] Examples of the nonionic surfactant include polyoxyalkylene alkyl aryl ethers, polyoxyalkylene alkyl ethers, polyoxyalkylene fatty acid esters, sorbitan fatty acid esters, silicone-based surfactants, acetylene alcohol-based surfactants, and fluorine-containing surfactants.

[0276] Examples of the polyoxyalkylene alkyl aryl ethers include polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene dodecylphenyl ether, and the like.

[0277] Examples of the polyoxyalkylene alkyl ethers include polyoxyethylene alkyl ethers such as polyoxyethylene oleyl ether and polyoxyethylene lauryl ether.

[0278] Examples of the polyoxyalkylene fatty acid esters include polyoxyethylene oleate, polyoxyethylene laurate, polyoxyethylene distearate, and the like.

[0279] Examples of the sorbitan fatty acid esters include sorbitan laurate, sorbitan monostearate, sorbitan monooleate, sorbitan sesquioleate, polyoxyethylene monooleate, and polyoxyethylene stearate.

[0280] Examples of the silicone-based surfactant include dimethylpolysiloxane and the like.

[0281] Examples of the acetylene alcohol surfactant include 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,6-dimethyl-4-octyne-3,6-diol, and 3,5-dimethyl-1-hexyne-3-ol.

[0282] Examples of the fluorine-containing surfactant include fluoroalkyl esters and the like.

[0283] (Crosslinking agent)

[0284] From the viewpoint of improving the above-mentioned barrier properties and pot life, and improving the alkali resistance to alkaline liquids (for example, alkaline detergents, etc.), the gas barrier coating material of the third embodiment preferably further contains a crosslinking agent.

[0285] As such a crosslinking agent, a known crosslinking agent can be used, preferably comprising one or more compounds selected from the group consisting of epoxy silane compounds, carbodiimide compounds and isocyanate compounds, more preferably comprising one or more compounds selected from the group consisting of epoxy silane compounds and carbodiimide compounds.

[0286] In the gas barrier coating material of the third embodiment, when the solid content of the gas barrier coating material as a whole is set to 100 mass%, the content of the crosslinking agent is preferably 0.010 mass% or more, and more preferably 0.015 mass% or more. By making the content of the crosslinking agent equal to or greater than the above lower limit, the alkali resistance of the gas barrier layer formed by the gas barrier coating material of the third embodiment becomes more suitable.

[0287] The content of the crosslinking agent is preferably 2% by mass or less, more preferably 1% by mass or less, and further preferably 0.05% by mass or less. By setting the content of the crosslinking agent to be below the upper limit, the productivity and barrier properties of the gas barrier coating material of the third embodiment become more suitable.

[0288] The gas barrier coating material of the third embodiment may contain additives other than the above-mentioned components, for example, various additives such as lubricants, slip agents, anti-blocking agents, antistatic agents, anti-fogging agents, pigments, dyes, and inorganic or organic fillers may be added.

[0289] In addition, from the viewpoint of improving the coating properties when applied as a gas barrier coating material, the solid content concentration of the gas barrier coating material of the third embodiment is preferably 0.5 to 15% by mass, more preferably 1 to 10% by mass, further preferably 1 to 5% by mass, and further preferably 1 to 3% by mass.

[0290] (physical properties)

[0291] In the gas barrier coating material of the third embodiment, for the cured product obtained by curing the gas barrier coating material, the composition ratio of Zn measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA is preferably 1.0 atomic% or more, more preferably 2.0 atomic% or more, further preferably 3.0 atomic% or more, further preferably 3.5 atomic% or more, and further preferably 3.7 atomic% or more. By making the composition ratio of Zn equal to or greater than the above lower limit, the barrier properties can be further improved.

[0292] The composition ratio of Zn is preferably 10.0 atomic % or less, more preferably 9.0 atomic % or less, further preferably 8.0 atomic % or less, further preferably 7.0 atomic % or less, further preferably 6.0 atomic % or less.

[0293] By setting the composition ratio of Zn to be equal to or less than the above upper limit, precipitation of Zn in the gas barrier coating material can be suppressed, and the pot life of the gas barrier coating material can be further improved.

[0294] In the gas barrier coating material of the third embodiment, for the cured product obtained by curing the gas barrier coating material, the P composition ratio measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA is preferably 0.05 atomic% or more, more preferably 0.10 atomic% or more, and further preferably 0.20 atomic% or more. By making the P composition ratio equal to or greater than the above lower limit, the barrier properties can be further improved.

[0295] The composition ratio of P is preferably 1.5 atomic % or less, more preferably 1.3 atomic % or less, further preferably 1.0 atomic % or less, and further preferably 0.8 atomic % or less.

[0296] By setting the composition ratio of P to be equal to or less than the above upper limit, the reaction with Zn in the gas barrier coating material can be suppressed, and the pot life of the gas barrier coating material can be further improved.

[0297] Here, the cured product of the gas barrier coating material can be obtained, for example, by coating the gas barrier coating material on a biaxially stretched polyethylene terephthalate film so that the coating amount after drying becomes 0.3 μm, and then heat treating the film at 130° C. for 60 seconds.

[0298] An example of specific conditions of the above-mentioned X-ray photoelectron spectroscopy analysis is shown.

[0299] Analyzer: AXIS-NOVA manufactured by KRATOS

[0300] X-ray source: monochromatized Al-Kα

[0301] X-ray source output power: 15kV, 10mA

[0302] Analysis area: 300×700μm

[0303] A neutralizing electron gun is used for charge correction during analysis.

[0304] In order to analyze the interior of the cured gas barrier coating material, it is desirable to sputter-etch the surface of the cured gas barrier coating material before analysis. Among them, in order to reduce the damage to the cured gas barrier coating material caused by etching, etching based on an Ar-gas cluster ion beam source is desirable.

[0305] The detection element is determined by wide scanning, and the spectrum of each element is obtained by narrow scanning. Then, the background calculated by Shirley method is removed from the obtained spectrum, and the atomic composition ratio (atomic %) of the detection element is calculated based on the obtained peak area using the relative sensitivity coefficient method.

[0306] (Gas Barrier Laminate)

[0307] Figure 1 The present invention is a cross-sectional view schematically showing an example of the structure of the gas barrier layered product in the first to third embodiments (hereinafter, also collectively referred to as the present embodiment). The gas barrier layered product in the present embodiment comprises a substrate layer 101 and a gas barrier layer 103 provided on at least one side of the substrate layer 101, wherein the gas barrier layer 103 comprises a cured product of the gas barrier coating material.

[0308] In this case, the gas barrier layered product of the present embodiment preferably further includes an inorganic layer 102 provided between the base layer 101 and the gas barrier layer 103 .

[0309] Hereinafter, the specific configuration of each layer in the gas barrier layered product according to the present embodiment will be described in detail.

[0310] (Gas barrier layer)

[0311] Specifically, the gas barrier layer 103 can be produced by applying and curing a gas barrier coating material. In this way, the gas barrier layer 103 in the present embodiment can be made into a layer including a cured product of the gas barrier coating material.

[0312] The gas barrier coating material according to the present embodiment can be obtained as follows.

[0313] First, a volatile base is appropriately added to a polycarboxylic acid to completely or partially neutralize the carboxyl groups of the polycarboxylic acid, and then a Zn compound and an appropriate carbonate-based ammonium salt are mixed to form a metal salt in all or part of the carboxyl groups of the polycarboxylic acid neutralized with the volatile base and in the carboxyl groups of the polycarboxylic acid not neutralized with the volatile base.

[0314] Then, a polyamine compound is further added to obtain the gas barrier coating material of the present embodiment. By mixing the polycarboxylic acid, the Zn compound, the appropriate carbonate-based ammonium salt and the polyamine compound in such a step, the generation of agglomerates can be suppressed, and a more uniform gas barrier coating material can be obtained. As a result, the dehydration condensation reaction between the -COO- group contained in the polycarboxylic acid and the amino group contained in the polyamine compound can be more effectively performed.

[0315] The details are as follows: Hereinafter, the case where a volatile base and a carbonate-based ammonium salt are blended in a gas barrier coating material will be described as an example.

[0316] First, a completely or partially neutralized solution of the carboxyl groups constituting the polycarboxylic acid is prepared.

[0317] A volatile base is added to the polycarboxylic acid to completely or partially neutralize the carboxyl groups of the polycarboxylic acid. By neutralizing the carboxyl groups of the polycarboxylic acid, gelation caused by the reaction of the carboxyl groups constituting the polycarboxylic acid with the amino groups constituting the Zn compound and the polyamine compound when the Zn compound and the polyamine compound are added can be effectively prevented, thereby obtaining a more uniform gas barrier coating material.

[0318] Next, a Zn compound and a carbonate-based ammonium salt are added and dissolved, and the generated Zn ions form a Zn salt with the -COO- group constituting the polycarboxylic acid. At this time, the -COO- group that forms a salt with the Zn ion refers to both the above-mentioned carboxyl group that has not been neutralized with the base and the -COO- group that has been neutralized with the base. In the case of the -COO- group that has been neutralized with the base, the Zn ions contained in the above-mentioned Zn compound are replaced and coordinated to form a Zn salt of the -COO- group. Then, after the Zn salt is formed, a polyamine compound and a phosphorus compound or its salt (in the case of a phosphorus compound or its salt) are further added, thereby obtaining a gas barrier coating material.

[0319] The gas barrier coating material produced in this manner is applied to the substrate layer 101, the inorganic layer 102, or the intermediate layer between the inorganic layer 102 and the gas barrier layer 103 formed on the inorganic layer 102, and dried and cured to form the gas barrier layer 103. At this time, the -COO- group constituting the polycarboxylic acid forms a metal crosslink with the Zn of the Zn salt, and the amino group constituting the polyamine forms an amide crosslink, so that the gas barrier layer 103 having excellent gas barrier properties can be obtained. A more detailed method for producing the gas barrier layer 103 will be described later.

[0320] From the viewpoint of improving barrier properties, the thickness of the gas barrier layer 103 after drying and curing is preferably 0.05 μm or more, more preferably 0.07 μm or more, and even more preferably 0.1 μm or more.

[0321] From the viewpoint of reducing the thickness of the entire gas barrier laminate, the thickness of the gas barrier layer 103 after drying and curing is preferably 10 μm or less, more preferably 5 μm or less, further preferably 1 μm or less, and further preferably 0.5 μm or less.

[0322] (Base material layer)

[0323] The substrate layer 101 may be a single layer or may be two or more layers. The shape of the substrate layer 101 is not limited, and examples thereof include a sheet or film shape, a tray, a cup, a hollow body, and the like.

[0324] As the material of the substrate layer 101, any material can be used without limitation as long as the inorganic layer 102 described later can be stably formed on the substrate layer 101 and a solution of a gas barrier coating material can be coated on the upper part of the inorganic layer 102. As the material of the substrate layer 101, for example, resins such as thermosetting resins and thermoplastic resins, organic materials such as paper, inorganic materials such as glass, pottery, ceramics, silicon oxide, silicon nitride oxide, silicon nitride, cement, aluminum, aluminum oxide, iron, copper, stainless steel and other metals, and a substrate layer of a multilayer structure formed by a combination of organic materials or a combination of organic materials and inorganic materials. Among these, for example, in the case of various film applications such as packaging materials and panels, it is preferred to use a plastic film of at least one selected from the group consisting of thermosetting resins and thermoplastic resins, or an organic material such as paper.

[0325] As the thermosetting resin, a known thermosetting resin can be used, for example, epoxy resin, unsaturated polyester resin, phenol resin, urea-melamine resin, polyurethane resin, silicone resin, polyimide, etc. can be mentioned.

[0326] As the thermoplastic resin, known thermoplastic resins can be used. For example, polyolefins (polyethylene, polypropylene, poly(4-methyl-1-pentene), poly(1-butene), etc.), polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyamides (nylon-6, nylon-66, poly(m-xylylene adipamide), etc.), polyvinyl chloride, polyimide, ethylene-vinyl acetate copolymer or its saponified product, polyvinyl alcohol, polyacrylonitrile, polycarbonate, polystyrene, ionomer, fluororesin or mixtures thereof can be cited.

[0327] Among these, from the viewpoint of improving transparency, one or more resins selected from the group consisting of polypropylene, polyethylene terephthalate (PET), polyethylene naphthalate, polyamide, polyimide, and polybutylene terephthalate are preferred.

[0328] In addition, from the viewpoint of excellent pinhole resistance, crack resistance, heat resistance, etc., one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate are preferred. From the same viewpoint, the base material layer 101 is preferably a layer containing one or more resins selected from the group consisting of polyamide, polyethylene terephthalate, and polybutylene terephthalate, and more preferably a layer containing one or more resins.

[0329] In addition, when a hygroscopic material such as polyamide is used in the substrate layer 101, in the gas barrier layer stack, the substrate layer 101 absorbs moisture and swells, and the gas barrier performance under high humidity, the gas barrier performance after boiling treatment, and the gas barrier performance when filled with acidic contents are easily reduced. However, in the present embodiment, even when a hygroscopic material is used as the substrate layer 101, the reduction in the gas barrier performance of the gas barrier layer stack under high humidity and the reduction in the gas barrier performance after boiling treatment can be appropriately suppressed.

[0330] Alternatively, the base layer 101 may be formed by stretching a film made of a thermosetting resin or a thermoplastic resin in at least one direction, preferably in two directions.

[0331] From the viewpoint of excellent transparency, rigidity and heat resistance, the substrate layer 101 is preferably a biaxially stretched film formed from one or more thermoplastic resins selected from the group consisting of polypropylene, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyimide and polybutylene terephthalate, and more preferably a biaxially stretched film formed from one or more thermoplastic resins selected from the group consisting of polyamide, polyethylene terephthalate and polybutylene terephthalate.

[0332] In addition, the surface of the base layer 101 may be coated with polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, acrylic resin, urethane resin, or the like.

[0333] The substrate layer 101 may be subjected to a surface treatment to improve adhesion to the gas barrier layer 103. Specifically, the surface of the substrate layer 101 facing the gas barrier layer 103 may be subjected to a surface activation treatment such as corona treatment, flame treatment, plasma treatment, or primer coating treatment.

[0334] From the viewpoint of obtaining good film properties, the thickness of the substrate layer 101 is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and is preferably 1000 μm or less, more preferably 500 μm or less, further preferably 300 μm or less.

[0335] (Inorganic layer)

[0336] The gas barrier layered product of the present embodiment preferably further includes an inorganic layer 102 provided between the base layer 101 and the gas barrier layer 103 .

[0337] Examples of the inorganic material constituting the inorganic material layer 102 include metals, metal oxides, metal nitrides, metal fluorides, metal oxynitrides, and the like that can form a thin film having barrier properties.

[0338] As inorganic substances constituting the inorganic layer 102, for example, there can be cited one or more of the single substances, oxides, nitrides, fluorides, or oxynitrides of elements in Group 2A of the periodic table, such as beryllium, magnesium, calcium, strontium, and barium; transition elements in the periodic table, such as titanium, zirconium, ruthenium, hafnium, and tantalum; elements in Group 2B of the periodic table, such as zinc; elements in Group 3A of the periodic table, such as aluminum, gallium, indium, and thallium; elements in Group 4A of the periodic table, such as silicon, germanium, and tin; and elements in Group 6A of the periodic table, such as selenium and tellurium.

[0339] It should be noted that, in the present embodiment, the group name of the periodic table of elements of the inorganic layer 102 is expressed in the old CAS format.

[0340] Among the above-mentioned inorganic substances, one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum are preferred, and aluminum oxide is more preferred, from the viewpoint of excellent balance between barrier properties and cost.

[0341] It should be noted that silicon oxide may contain silicon monoxide and silicon monoxide in addition to silicon dioxide.

[0342] The inorganic layer 102 is formed of the above-mentioned inorganic substance. From the viewpoint of excellent balance between barrier properties and cost, the inorganic layer 102 preferably includes an aluminum oxide layer composed of aluminum oxide.

[0343] The inorganic layer 102 may be composed of a single inorganic layer or a plurality of inorganic layers. In addition, when the inorganic layer 102 is composed of a plurality of inorganic layers, they may be composed of the same type of inorganic layers or of different types of inorganic layers.

[0344] From the perspective of achieving a balance between improved barrier properties and improved operability, the thickness of the inorganic layer 102 is, for example, greater than 1 nm, preferably greater than 4 nm, and, for example, less than 1000 nm, preferably less than 500 nm, more preferably less than 100 nm, further preferably less than 50 nm, further preferably less than 30 nm, further preferably less than 15 nm, further preferably less than 10 nm.

[0345] Here, the thickness of the inorganic substance layer 102 can be obtained by observing an image using a transmission electron microscope or a scanning electron microscope, for example.

[0346] The method for forming the inorganic layer 102 is not limited. For example, the inorganic layer 102 can be formed on one or both sides of the substrate layer 101 by vacuum evaporation, ion plating, sputtering, chemical vapor deposition, physical vapor deposition, chemical vapor deposition (CVD), plasma CVD, sol-gel method, etc. Among them, film formation under reduced pressure by sputtering, ion plating, chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma CVD, etc. is ideal. Therefore, it is predicted that chemically active molecular species containing silicon such as silicon nitride and silicon oxynitride react quickly, thereby improving the smoothness of the surface of the inorganic layer 102 and reducing pores. In order to quickly carry out these bonding reactions, it is ideal that the inorganic atoms and compounds are chemically active molecular species or atomic species.

[0347] Furthermore, from the viewpoint of improving the balance between the barrier properties and productivity of the gas barrier laminate, the inorganic substance layer 102 is preferably a vapor-deposited film.

[0348] From the perspective of improving the balance between the barrier properties and productivity of the gas barrier laminate, the inorganic layer 102 is a vapor-deposited film provided on the substrate layer 101, or when there is an intermediate layer between the substrate layer 101 and the inorganic layer 102, it is a vapor-deposited film provided on the intermediate layer, and is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum, and is preferably composed of aluminum oxide.

[0349] (Base coating)

[0350] A primer layer may be provided between the substrate layer 101 and the inorganic layer 102. However, from the viewpoint that the gas barrier coating material in the present embodiment has sufficient barrier properties even without a primer layer, and that productivity is improved by omitting the step of providing a primer layer, it is preferred not to provide a primer layer.

[0351] When a primer layer is provided, from the viewpoint of improving the adhesion between the substrate layer 101 and the inorganic layer 102, the material of the primer layer may be, for example, one or more selected from the group consisting of polyurethane resin, polyester resin, oxazoline resin, and (meth)acrylic resin.

[0352] Examples of polyurethane resins include various polyurethane resins, polyurethane polyurea resins, and prepolymers thereof. Specific examples of such urethane resins include: reaction products of diisocyanate components such as toluene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, and dicyclohexyl diisocyanate with diol components such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexanedimethanol, bisphenol, polyester diol, polyether diol, polycarbonate diol, and polyethylene glycol; reaction products of urethane prepolymers having an isocyanate group at the end and amino compounds, aminosulfonates, polyhydroxycarboxylic acids, acidic sulfurous acids, and the like; and the like.

[0353] As the polyester resin used in the primer layer, various polyester resins and their modified products can be exemplified. Specific examples of such polyester resins include reaction products of polycarboxylic acid components such as terephthalic acid, phthalic acid, isophthalic acid, trimellitic acid, pyromellitic acid, 2-sulfoisophthalic acid, 5-sulfoisophthalic acid, adipic acid, sebacic acid, succinic acid, and dodecanedioic acid, and diol components such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexanedimethanol, and bisphenol, and also include modified products of acrylic resins, epoxy resins, and the like.

[0354] When an oxazoline resin is used for the primer layer, the primer layer is preferably composed of an oxazoline-based resin composition containing an oxazoline group-containing aqueous polymer, an aqueous (meth)acrylic resin, and an aqueous polyester resin.

[0355] From the viewpoint of obtaining good adhesion, the thickness of the primer layer is preferably 0.001 μm or more, more preferably 0.005 μm or more, further preferably 0.01 μm or more, further preferably 0.05 μm or more, further preferably 0.1 μm or more, and further preferably 0.2 μm or more.

[0356] From the viewpoint of economic efficiency, the thickness of the primer layer is preferably 1.0 μm or less, more preferably 0.6 μm or less, further preferably 0.5 μm or less, and may be, for example, 0.4 μm or less, or 0.3 μm or less.

[0357] (Adhesive layer)

[0358] The gas barrier layered product may further include an adhesive layer.

[0359] The adhesive layer is, for example, provided between the gas barrier layer 103 and the upper layer of the gas barrier layer 103. In addition, when the upper layer is formed by a plurality of layers, an adhesive layer may be provided between the plurality of layers. Here, the upper layer of the gas barrier layer 103 refers to a layer stacked on the surface of the gas barrier layer 103 that is opposite to the surface of the inorganic layer 102.

[0360] The adhesive layer may contain a known adhesive. As the adhesive, there may be mentioned: a laminating adhesive composed of organic titanium resin, polyethyleneimine resin, urethane resin, epoxy resin, acrylic resin, polyester resin, oxazoline-containing resin, modified silicone resin, alkyl titanate, polyester polybutadiene, etc.; or one-component or two-component polyol and polyisocyanate, water-based urethane, ion cross-linked polymer, etc. Alternatively, a water-based adhesive with acrylic resin, vinyl acetate resin, urethane resin, polyester resin, etc. as the main raw material may be used.

[0361] In addition, other additives such as a curing agent and a silane coupling agent may be added to the adhesive depending on the application of the gas barrier layered product 100. When the gas barrier layered product is used for hot water treatment such as boiling, from the viewpoint of heat resistance and water resistance, a dry lamination adhesive represented by a polyurethane adhesive is preferred, and a solvent-based two-component curing polyurethane adhesive is more preferred.

[0362] (Method for producing gas barrier laminate)

[0363] In this embodiment, the manufacturing method of the gas barrier layer stack 100 includes, for example: a process of preparing a substrate layer 101; a process of forming an inorganic layer 102 on the substrate layer 101; and a process of forming a gas barrier layer 103 on the upper part of the substrate layer 101 on which the inorganic layer 102 is formed.

[0364] In the step of forming the inorganic layer 102 on the base layer 101 , for example, the above-described method for forming the inorganic layer 102 can be used.

[0365] The process of forming the gas barrier layer 103 includes, for example: applying a gas barrier coating material to the inorganic layer 102, followed by drying to obtain a coating layer; and heating the coating layer to allow the carboxyl groups contained in the polycarboxylic acid and the amino groups contained in the polyamine compound to undergo a dehydration condensation reaction to form a gas barrier layer 103 having an amide bond.

[0366] The method of applying the gas barrier coating material to the inorganic layer 102 can be any common method without limitation. For example, the coating method can be a method using a known coating machine such as a Meyer rod coater, an air knife coater, a direct gravure coater, a gravure offset printer, a curved gravure coater, a reverse gravure printer, and a jet nozzle type gravure coater, a top feed reverse coater, a bottom feed reverse coater, and a nozzle feed reverse coater, a reverse roll coater, a five-roll coater, a lip coater, a rod coater, a rod reverse coater, a die coater, and the like.

[0367] Regarding drying and heat treatment, heat treatment may be performed after drying, or drying and heat treatment may be performed simultaneously.

[0368] The method of drying and heating treatment is not limited as long as the effect of the present invention can be obtained, and it can be a method that can cure the gas barrier coating material or a method that can heat the cured gas barrier coating material. For example, there can be cited methods based on convection heat transfer such as ovens and dryers; methods based on conduction heat transfer such as heating rollers; methods based on radiation heat transfer using electromagnetic waves such as infrared, far-infrared and near-infrared heaters; and methods based on internal heating such as microwaves. As a device for drying and heating treatment, from the viewpoint of manufacturing efficiency, it is preferably a device that can perform both drying and heating treatment. Specifically, from the viewpoint of being able to be used for various purposes such as drying, heating, and annealing, it is preferred to use a hot air oven, and from the viewpoint of excellent heat conduction efficiency to the film, it is preferred to use a heating roller. In addition, the methods for drying and heating treatment can also be appropriately combined. Specifically, a hot air oven and a heating roller can be used together. For example, when the gas barrier coating material is dried by a hot air oven and then heated by a heating roller, the time of the heating treatment process is shortened, which is preferred from the viewpoint of manufacturing efficiency. In addition, it is preferred to perform the drying and heating treatment only using a hot air oven.

[0369] Regarding the heat treatment conditions, for example, the heat treatment temperature is 80 to 180° C. and the heat treatment time is 1 second to 5 minutes, preferably the heat treatment temperature is 90 to 160° C. and the heat treatment time is 10 seconds to 3 minutes, more preferably the heat treatment temperature is 100° C. to 150° C. and the heat treatment time is 15 seconds to 2 minutes, and further preferably the heat treatment temperature is 110° C. to 140° C. and the heat treatment time is 30 seconds to 90 seconds. In addition, by using a heating roller in combination as described above, a short-time heat treatment can be achieved.

[0370] In order to efficiently carry out the dehydration condensation reaction between the -COO- group contained in the polycarboxylic acid and the amino group contained in the polyamine compound, it is important to adjust the heat treatment temperature and heat treatment time according to the coating amount of the gas barrier coating material.

[0371] By drying and heat-treating the gas barrier coating material, the carboxyl groups of the polycarboxylic acid react with the polyamine and the Zn compound to form covalent bonds and ion crosslinks, thereby forming a gas barrier layer 103 having good gas barrier properties even after retorting.

[0372] In the present embodiment, the gas barrier layered product has excellent gas barrier properties and can be suitably used as a packaging material, for example, a packaging material for various medical uses, industrial uses, daily miscellaneous goods uses, and particularly a packaging material for food that requires high gas barrier properties.

[0373] The gas barrier laminate in the present embodiment can be suitably used as, for example, a vacuum heat insulating film requiring high barrier performance, a sealing film for sealing an electroluminescent element, a solar cell, or the like, or the like.

[0374] In the present embodiment, specific examples of the laminate structure including the gas barrier layered product are shown below.

[0375] (Laminate Structure Example 1) Base material layer 101 (PET base material) / gas barrier layer 103 / adhesive layer / polyolefin layer

[0376] (Laminate Structure Example 2) Base material layer 101 (PET base material) / inorganic material layer 102 (aluminum oxide vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyolefin layer

[0377] (Laminate structure example 3) Base material layer 101 (PET base material) / inorganic material layer 102 (alumina vapor-deposited layer) / gas barrier layer 103 / adhesive layer / polyamide layer / adhesive layer / polyolefin layer

[0378] Here, by including a polyolefin layer composed of polyolefins such as polyethylene, polypropylene, poly(4-methyl-1-pentene), and poly(1-butene) in the laminate structure, the pinhole resistance, crack resistance, and heat resistance of the gas barrier laminate can be improved, and the reduction in gas barrier performance under high humidity and the reduction in gas barrier performance after boiling treatment can be further suppressed.

[0379] As mentioned above, although embodiment of this invention is described with reference to drawings, these are examples of this invention, and various structures other than the above-mentioned can also be adopted.

[0380] Example

[0381] Hereinafter, the present embodiment will be described in detail with reference to Examples and Comparative Examples. It should be noted that the present embodiment is not limited at all by the description of these Examples.

[0382] (Example 1A)

[0383] (1) Preparation of gas barrier coating materials

[0384] Polyacrylic acid, 10% by mass ammonia water (manufactured by Wako Pure Chemical Industries, Ltd.), and purified water were mixed so that ammonia became 250 equivalent % with respect to the carboxyl group of polyacrylic acid (manufactured by Toagosei Co., Ltd., product name: AC-10H, weight average molecular weight: 800,000), thereby obtaining an aqueous solution of ammonium polyacrylate having a concentration of 7.29% by mass.

[0385] Next, zinc oxide (manufactured by Kanto Chemical Co., Ltd.) and ammonium carbonate were added to the obtained aqueous solution of ammonium polyacrylate, mixed and stirred to prepare a mixed solution (AA). Here, the amount of zinc oxide added was set to an amount such that (the number of moles of zinc oxide in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "ZnO / PAA") became the value shown in Table 1. In addition, ammonium carbonate was set to an amount such that (the number of moles of carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of zinc oxide in the gas barrier coating material) became 1.5.

[0386] Next, purified water was added to polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., product name: SP-200, number average molecular weight: 10,000) to obtain a polyethyleneimine aqueous solution as a 10% solution.

[0387] Next, the mixed solution (AA) and the aqueous polyethyleneimine solution are mixed in a ratio of (the number of moles of amino groups contained in the polyethyleneimine in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "PEI / PAA") to a value shown in Table 1 to prepare a mixed solution (BA).

[0388] Purified water was further added to the mixed solution (BA) so that the solid content concentration became 1.5% by mass, and the mixture was stirred until a uniform solution was obtained. Then, a surfactant (polyoxyethylene lauryl ether, manufactured by Kao Corporation, trade name: EMULGEN 120) was mixed so that the solid content of the mixed solution (BA) became 0.3% by mass, thereby preparing a gas barrier coating material.

[0389] (Example 2A)

[0390] A gas barrier coating material was prepared in the same manner as in Example 1A except that the amount of zinc oxide added was changed so that ZnO / PAA had the values ​​shown in Table 1.

[0391] (Comparative Examples 1A, 2A)

[0392] A gas barrier coating material was prepared in the same manner as in Example 1A except that the amount of zinc oxide added was changed so that ZnO / PAA had the values ​​shown in Table 1.

[0393] At this time, ZnO / PAA being 0 means that zinc oxide is not added.

[0394] (Example 3A)

[0395] Polyacrylic acid, 10% by mass ammonia water (manufactured by Wako Pure Chemical Industries, Ltd.), and purified water were mixed so that ammonia became 250 equivalent % with respect to the carboxyl group of polyacrylic acid (manufactured by Toagosei Co., Ltd., product name: AC-10H, weight average molecular weight: 800,000), thereby obtaining an aqueous solution of ammonium polyacrylate having a concentration of 7.29% by mass.

[0396] Next, zinc oxide (manufactured by Kanto Chemical Co., Ltd.) and ammonium carbonate were added to the obtained aqueous solution of ammonium polyacrylate, mixed and stirred to prepare a mixed solution (AA). Here, the amount of zinc oxide added was set to an amount such that ZnO / PAA had the value shown in Table 1. In addition, the amount of ammonium carbonate was set to an amount such that (the number of moles of carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of zinc oxide in the gas barrier coating material) was 1.5.

[0397] Next, purified water was added to polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., product name: SP-200, number average molecular weight: 10,000) to obtain a polyethyleneimine aqueous solution as a 10% solution.

[0398] Separately, purified water was added to diammonium hydrogen phosphate ((NH 4 ) 2 HPO 4 manufactured by Kanto Chemical Co., Ltd.) to prepare a 10 mass % diammonium hydrogen phosphate solution.

[0399] Next, the mixed solution (AA), the polyethyleneimine aqueous solution and the diammonium hydrogen phosphate solution as a phosphorus introduction source are mixed in a ratio such that PEI / PAA becomes the value shown in Table 1 and (the number of moles of P contained in the phosphorus compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "P / PAA") becomes the value shown in Table 1 to prepare a mixed solution (BA).

[0400] Purified water was further added to the mixed solution (BA) so that the solid content concentration became 1.5% by mass, and the mixture was stirred until a uniform solution was obtained. Then, a surfactant (polyoxyethylene lauryl ether, manufactured by Kao Corporation, trade name: EMULGEN 120) was mixed so that the solid content of the mixed solution (BA) became 0.3% by mass, thereby preparing a gas barrier coating material.

[0401] (Example 4A)

[0402] A gas barrier coating material was prepared in the same manner as in Example 3A except that the amount of diammonium hydrogen phosphate solution added was changed so that P / PAA became the value shown in Table 1.

[0403] (Example 5A)

[0404] Oligomeric ammonium polyphosphate (manufactured by Yutian Co., Ltd., product number: water-soluble ammonium polyphosphate flame retardant NNA20, P2O5 content 59%) was added to purified water to prepare a 25 mass % oligomeric ammonium polyphosphate solution.

[0405] As a phosphorus introduction source, the above-mentioned oligomeric ammonium polyphosphate solution was used instead of the above-mentioned diammonium hydrogen phosphate solution, and the mixture was mixed in a ratio of (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter, these are also referred to as "P / PAA") to be the values ​​shown in Table 1. Except for this, a gas barrier coating material was prepared according to Example 3A.

[0406] (Examples 6A, 7A)

[0407] A gas barrier coating material was prepared in the same manner as in Example 5A except that the amount of the oligomeric ammonium polyphosphate solution added was changed so that P / PAA became the value shown in Table 1.

[0408] (Example 8A)

[0409] A gas barrier coating material was prepared in the same manner as in Example 6A, except that the amount of zinc oxide added was changed so that ZnO / PAA became the values ​​shown in Table 1 and an epoxy silane compound (manufactured by Shin-Etsu Silicone Co., Ltd., product number: KBM-403) as a cross-linking agent was mixed with the mixed solution (BA) in an amount of 0.020 mass % relative to the solid content of the mixed solution (BA).

[0410] (Example 9A)

[0411] A gas barrier coating material was prepared in the same manner as in Example 8A except that a carbodiimide compound (manufactured by Nisshinbo Chemical Co., Ltd., product number: CARBODILITE SV-02) was used as a crosslinking agent instead of epoxysilane.

[0412] (Example 10A)

[0413] A gas barrier coating material was prepared in the same manner as in Example 8A except that an isocyanate compound (manufactured by Mitsui Chemicals, Inc., product number: TAKENATE (registered trademark) WD726) was used as a cross-linking agent instead of epoxy silane.

[0414] (Example 11A)

[0415] A gas barrier coating material was prepared in the same manner as in Example 8A except that the amount of the oligomeric ammonium polyphosphate solution added was changed so that P / PAA would have the value shown in Table 1 and the amount of the crosslinking agent added was changed to 0.015 mass %.

[0416] [Production of Gas Barrier Laminated Material]

[0417] (Production of Gas Barrier Laminate 1A)

[0418] A biaxially stretched polyethylene terephthalate film (manufactured by UNITIKA LTD., PET12) with a thickness of 12 μm was used as a substrate, and the gas barrier coating material obtained in each example and each comparative example was applied to the corona-treated surface thereof using a Meyer bar so that the coating thickness after drying was 0.3 μm. Then, a heat treatment was performed at 130° C. for 60 seconds using a hot air dryer. Thus, a gas barrier laminate 1A was obtained.

[0419] (Production of Gas Barrier Laminated Layer 2A)

[0420] A biaxially stretched polyethylene terephthalate film (manufactured by UNITIKA LTD., PET12) with a thickness of 12 μm was used as a substrate. Aluminum was heated and evaporated on the corona-treated surface by high-frequency induction heating, and oxygen was introduced while vapor deposition was performed to form an aluminum oxide film with a thickness of 7 nm. Thus, an aluminum oxide vapor-deposited PET film was obtained. The water vapor permeability of the aluminum oxide vapor-deposited PET film was 1.5 g / (m 2 ·24h).

[0421] Next, the gas barrier coating material was applied on the deposited layer using a Meyer bar to a coating thickness of 0.3 μm after drying, and heat treated at 130° C. for 60 seconds using a hot air dryer to obtain a gas barrier laminate 2A.

[0422] [Preparation of test film]

[0423] (Preparation of Test Film 1A)

[0424] An ester adhesive (9 parts by mass of a polyurethane adhesive (Mitsui Chemicals, Inc., trade name: TAKELACA525S), 1 part by mass of an isocyanate curing agent (Mitsui Chemicals, Inc., trade name: TAKENATEA50), and 7.5 parts by mass of ethyl acetate) was applied to one side of a 70 μm thick unstretched polypropylene film (Mitsui Chemicals Tocello, Inc., trade name: RXC-22). Next, the barrier surface (the surface coated with the gas barrier coating material) of the gas barrier laminate 1A obtained in each of the examples and comparative examples was attached to the surface of the unstretched polypropylene film coated with the adhesive to obtain a test film 1A before steaming treatment.

[0425] (Preparation of Test Film 2A)

[0426] An ester adhesive (9 parts by mass of a polyurethane adhesive (Mitsui Chemicals, Inc., trade name: TAKELACA525S), 1 part by mass of an isocyanate curing agent (Mitsui Chemicals, Inc., trade name: TAKENATEA50), and 7.5 parts by mass of ethyl acetate) was applied to one side of a 70 μm thick unstretched polypropylene film (Mitsui Chemicals Tocello, Inc., trade name: RXC-22). Next, the barrier surface (the surface coated with the gas barrier coating material) of the gas barrier laminate 2A obtained in each of the embodiments and comparative examples was attached to the surface of the unstretched polypropylene film coated with the adhesive to obtain a test film 2A before steaming treatment.

[0427] (Preparation of Test Film 3A)

[0428] An ester adhesive (9 parts by mass of a polyurethane adhesive (manufactured by Mitsui Chemicals, trade name: TAKELAC A525S), 1 part by mass of an isocyanate curing agent (manufactured by Mitsui Chemicals, trade name: TAKENATEA50), and 7.5 parts by mass of ethyl acetate) was applied on both sides of a 15 μm thick nylon film (manufactured by UNITIKA LTD., trade name: EMBLEM ONBC). Next, the barrier surface (the surface coated with the gas barrier coating material) of the gas barrier laminate 2A obtained in each embodiment and each comparative example and a 60 μm thick unstretched polypropylene film (manufactured by Mitsui Chemicals Tocello, Inc., trade name: RXC-22) were attached to both sides of the nylon film to which the adhesive was applied, to obtain a test film 3A before steaming treatment.

[0429] [Evaluation method]

[0430] (Cooking treatment (water filling))

[0431] The test films 1A to 3A before the retort treatment obtained in the above [Preparation of test films] were folded back in a manner that the unstretched polypropylene film became the inner surface, and the two sides were heat-sealed to form a bag shape. Then, 70 mL of water was filled as the content, and the bag was made by heat-sealing the other side. It was retorted in a high-temperature and high-pressure retort sterilization device at 130° C. for 30 minutes. After the retort treatment, the water in the content was removed to obtain the retort treated (water filled) test films 1A to 3A.

[0432] (oxygen permeability [mL / (m 2 ·day·MPa)])

[0433] The oxygen permeability of the test films 1A to 2A before retorting and the test films 1A to 3A after retorting (water filling) obtained by the above method was measured using OX-TRAN2 / 21 manufactured by Mocon Co., Ltd. in accordance with JIS K 7126 at a temperature of 20°C and a humidity of 90% RH. The results are shown in Table 1. It should be noted that in the table, oxygen permeability [mL / (m 2 ·day·MPa)] is called OTR.

[0434] (Water vapor permeability [g / (m 2 ·sky)])

[0435] The test films 1A to 2A before retorting treatment and the test films 1A to 3A after retorting treatment (water filling) obtained by the above method were stacked so that the unstretched polypropylene film became the inner surface, and the gas barrier laminated film was folded back and heat-sealed on three sides to form a bag shape. Calcium chloride was added as the content, and the other side was heat-sealed to form a bag with a surface area of ​​0.01 m 2 The bags were made in the same manner and placed under the conditions of 40°C and 90% RH for 300 hours. The water vapor permeability was measured using the weight difference. The results are shown in Table 1. It should be noted that in the table, the water vapor permeability [g / (m 2 ·day)] is called WVTR.

[0436] (Laminated film immersion test)

[0437] The test films 1A to 3A obtained in the above [Preparation of test films] were folded back in a manner such that the unstretched polypropylene film became the inner surface, and heat-sealed to form a bag. The bagged test film was immersed in an alkaline detergent JOY (registered trademark) (manufactured by P&G) diluted 10 times with tap water. After 1 week, the test film was visually confirmed to evaluate whether delamination occurred. The results are shown in Table 1.

[0438] A: No interlayer delamination occurs

[0439] B: Delamination between layers occurs

[0440] [Table 1]

[0441]

[0442] According to Table 1, in each of the Examples, a gas barrier material having improved balance between productivity and barrier properties can be obtained by heat treatment at low temperature and for a short time, as compared with each of the Comparative Examples.

[0443] Furthermore, by adding a polyphosphoric acid compound, the water vapor permeability can be further improved.

[0444] Furthermore, by adding a cross-linking agent, the alkali resistance of the laminated film can be improved.

[0445] (Example 1B)

[0446] (1) Preparation of gas barrier coating materials

[0447] Polyacrylic acid, 10% by mass ammonia water (manufactured by Wako Pure Chemical Industries, Ltd.), and purified water were mixed so that ammonia became 250 equivalent % with respect to the carboxyl group of polyacrylic acid (manufactured by Toagosei Co., Ltd., product name: AC-10H, weight average molecular weight: 800,000), thereby obtaining an aqueous solution of ammonium polyacrylate having a concentration of 7.29% by mass.

[0448] Next, zinc oxide (manufactured by Kanto Chemical Co., Ltd.) and ammonium carbonate were added to the obtained aqueous solution of ammonium polyacrylate, mixed and stirred to prepare a mixed solution (AB). Here, the amount of zinc oxide added was set to an amount such that (the number of moles of zinc oxide in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "ZnO / PAA") became the value shown in Table 2. In addition, ammonium carbonate was set to an amount such that (the number of moles of carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of zinc oxide in the gas barrier coating material) became 1.5.

[0449] Next, purified water was added to polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., product name: SP-200, number average molecular weight: 10,000) to obtain a polyethyleneimine aqueous solution as a 10% solution.

[0450] Next, the mixed solution (AB) and the aqueous polyethyleneimine solution are mixed in a ratio of (the number of moles of amino groups contained in the polyethyleneimine in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "PEI / PAA") to a value shown in Table 2 to prepare a mixed solution (BB).

[0451] Purified water was further added to the mixed solution (BB) so that the solid content concentration became 1.5% by mass, and the mixture was stirred until a uniform solution was obtained. Then, a surfactant (polyoxyethylene lauryl ether, manufactured by Kao Corporation, trade name: EMULGEN 120) was mixed so that the solid content of the mixed solution (BB) became 0.3% by mass, thereby preparing a gas barrier coating material.

[0452] (Example 2B)

[0453] A gas barrier coating material was prepared in the same manner as in Example 1B except that the amount of zinc oxide added was changed so that ZnO / PAA had the values ​​shown in Table 2.

[0454] (Comparative Examples 1B, 2B)

[0455] A gas barrier coating material was prepared in the same manner as in Example 1B except that the amount of zinc oxide added was changed so that ZnO / PAA had the values ​​shown in Table 2.

[0456] At this time, ZnO / PAA being 0 means that zinc oxide is not added.

[0457] (Example 3B)

[0458] Polyacrylic acid, 10% by mass ammonia water (manufactured by Wako Pure Chemical Industries, Ltd.), and purified water were mixed so that ammonia became 250 equivalent % with respect to the carboxyl group of polyacrylic acid (manufactured by Toagosei Co., Ltd., product name: AC-10H, weight average molecular weight: 800,000), thereby obtaining an aqueous solution of ammonium polyacrylate having a concentration of 7.29% by mass.

[0459] Next, zinc oxide (manufactured by Kanto Chemical Co., Ltd.) and ammonium carbonate were added to the obtained aqueous solution of ammonium polyacrylate, mixed and stirred to prepare a mixed solution (AB). Here, the amount of zinc oxide added was set to an amount such that ZnO / PAA had the value shown in Table 2. In addition, the amount of ammonium carbonate was set to an amount such that (the number of moles of carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of zinc oxide in the gas barrier coating material) was 1.5.

[0460] Next, purified water was added to polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., product name: SP-200, number average molecular weight: 10,000) to obtain a polyethyleneimine aqueous solution as a 10% solution.

[0461] Separately, purified water was added to diammonium hydrogen phosphate ((NH 4 ) 2 HPO 4 manufactured by Kanto Chemical Co., Ltd.) to prepare a 10 mass % diammonium hydrogen phosphate solution.

[0462] Next, the mixed solution (AB), the polyethyleneimine aqueous solution and the diammonium hydrogen phosphate solution as a phosphorus introduction source are mixed in a ratio such that PEI / PAA becomes the value shown in Table 2 and (the number of moles of P contained in the phosphorus compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "P / PAA") becomes the value shown in Table 2 to prepare a mixed solution (BB).

[0463] Purified water was further added to the mixed solution (BB) so that the solid content concentration became 1.5% by mass, and the mixture was stirred until a uniform solution was obtained. Then, a surfactant (polyoxyethylene lauryl ether, manufactured by Kao Corporation, trade name: EMULGEN 120) was mixed so that the solid content of the mixed solution (BB) became 0.3% by mass, thereby preparing a gas barrier coating material.

[0464] (Example 4B)

[0465] A gas barrier coating material was prepared in the same manner as in Example 3B except that the amount of diammonium hydrogen phosphate solution added was changed so that P / PAA would have the value shown in Table 2.

[0466] (Example 5B)

[0467] Oligomeric ammonium polyphosphate (manufactured by Yutian Co., Ltd., product number: water-soluble ammonium polyphosphate flame retardant NNA20, P2O5 content 59%) was added to purified water to prepare a 25 mass % oligomeric ammonium polyphosphate solution.

[0468] As a phosphorus introduction source, the above-mentioned oligomeric ammonium polyphosphate solution was used instead of the above-mentioned diammonium hydrogen phosphate solution, and the (number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter, they are also referred to as "P / PAA") were mixed in a ratio of the values ​​shown in Table 2. Except for this, the gas barrier coating material was prepared according to Example 3B.

[0469] (Examples 6B, 7B)

[0470] A gas barrier coating material was prepared in the same manner as in Example 5B except that the amount of the oligomeric ammonium polyphosphate solution added was changed so that P / PAA would have the value shown in Table 2.

[0471] (Example 8B)

[0472] A gas barrier coating material was prepared in the same manner as in Example 6B, except that the amount of zinc oxide added was changed so that ZnO / PAA became the values ​​shown in Table 2 and an epoxy silane compound (manufactured by Shin-Etsu Silicone Co., Ltd., product number: KBM-403) as a cross-linking agent was mixed with the mixed solution (BB) in an amount of 0.020 mass % relative to the solid content of the mixed solution (BB).

[0473] (Example 9B)

[0474] A gas barrier coating material was prepared in the same manner as in Example 8B except that a carbodiimide compound (manufactured by Nisshinbo Chemical Co., Ltd., product number: CARBODILITE SV-02) was used as a crosslinking agent instead of epoxysilane.

[0475] (Example 10B)

[0476] A gas barrier coating material was prepared in the same manner as in Example 8B except that an isocyanate compound (manufactured by Mitsui Chemicals, Inc., product number: TAKENATE (registered trademark) WD726) was used as the cross-linking agent instead of epoxy silane.

[0477] (Example 11B)

[0478] A gas barrier coating material was prepared in the same manner as in Example 8B except that the amount of the oligomeric ammonium polyphosphate solution added was changed so that P / PAA became the value shown in Table 2 and the amount of the crosslinking agent added was changed to 0.015 mass %.

[0479] [Production of Gas Barrier Laminated Material]

[0480] (Production of Gas Barrier Laminate 1B)

[0481] A biaxially stretched polyethylene terephthalate film (manufactured by UNITIKA LTD., PET12) with a thickness of 12 μm was used as a substrate, and the gas barrier coating material obtained in each Example and each Comparative Example was applied to the corona-treated surface thereof using a Meyer bar so that the coating thickness after drying was 0.3 μm. Then, a heat treatment was performed at 130° C. for 60 seconds using a hot air dryer. Thus, a gas barrier laminate 1B was obtained.

[0482] (Production of Gas Barrier Laminated Layer 2B)

[0483] A biaxially stretched polyethylene terephthalate film (manufactured by UNITIKA LTD., PET12) with a thickness of 12 μm was used as a substrate. Aluminum was heated and evaporated on the corona-treated surface by high-frequency induction heating, and oxygen was introduced while vapor deposition was performed to form an aluminum oxide film with a thickness of 7 nm. Thus, an aluminum oxide vapor-deposited PET film was obtained. The water vapor permeability of the aluminum oxide vapor-deposited PET film was 1.5 g / (m 2 ·24h).

[0484] Next, the gas barrier coating material was applied on the deposited layer using a Meyer bar to a coating thickness of 0.3 μm after drying, and heat treated at 130° C. for 60 seconds using a hot air dryer to obtain a gas barrier laminate 2B.

[0485] [Preparation of test film]

[0486] (Preparation of Test Film 1B)

[0487] An ester adhesive (9 parts by mass of a polyurethane adhesive (Mitsui Chemicals, Inc., trade name: TAKELACA525S), 1 part by mass of an isocyanate curing agent (Mitsui Chemicals, Inc., trade name: TAKENATEA50), and 7.5 parts by mass of ethyl acetate) was applied to one side of an unstretched polypropylene film having a thickness of 70 μm (manufactured by Mitsui Chemicals Tocello, Inc.). Next, the barrier surface (the surface coated with the gas barrier coating material) of the gas barrier laminate 1B obtained in each of the embodiments and comparative examples was attached to the surface of the unstretched polypropylene film coated with the adhesive to obtain a test film 1B before steaming treatment.

[0488] (Preparation of Test Film 2B)

[0489] An ester adhesive (9 parts by mass of a polyurethane adhesive (Mitsui Chemicals, Inc., trade name: TAKELACA525S), 1 part by mass of an isocyanate curing agent (Mitsui Chemicals, Inc., trade name: TAKENATEA50), and 7.5 parts by mass of ethyl acetate) was applied to one side of a 70 μm thick unstretched polypropylene film (Mitsui Chemicals Tocello, Inc., trade name: RXC-22). Next, the barrier surface (the surface coated with the gas barrier coating material) of the gas barrier laminate 2B obtained in each of the embodiments and comparative examples was attached to the surface of the unstretched polypropylene film coated with the adhesive to obtain a test film 2B before steaming treatment.

[0490] (Preparation of Test Film 3B)

[0491] An ester adhesive (9 parts by mass of a polyurethane adhesive (manufactured by Mitsui Chemicals, trade name: TAKELAC A525S), 1 part by mass of an isocyanate curing agent (manufactured by Mitsui Chemicals, trade name: TAKENATEA50), and 7.5 parts by mass of ethyl acetate) was applied on both sides of a 15 μm thick nylon film (manufactured by UNITIKA LTD., trade name: EMBLEM ONBC). Next, the barrier surface (the surface coated with the gas barrier coating material) of the gas barrier laminate 2B obtained in each embodiment and each comparative example and a 60 μm thick unstretched polypropylene film (manufactured by Mitsui Chemicals Tocello, Inc., trade name: RXC-22) were attached to both sides of the nylon film to which the adhesive was applied, to obtain a test film 3B before steaming treatment.

[0492] [Evaluation method]

[0493] (XPS analysis)

[0494] The coating film surface was analyzed using a sample obtained by cutting the gas barrier layered product 2B obtained in each Example and each Comparative Example into a size of 1×1 cm.

[0495] The surface of the gas barrier layer in the sample obtained by cutting the gas barrier laminate 2B obtained in each embodiment and each comparative example into 1×1 cm (the surface coated with the gas barrier coating material) was subjected to sputtering etching based on an Ar-gas cluster ion beam source. Then, the detection element was determined by wide scanning under the following measurement conditions, and the spectrum was obtained for each element by narrow scanning. Finally, the background obtained by the Shirley method was removed from the obtained spectrum, and the atomic composition ratio (atomic%) of the detected element was calculated based on the obtained peak area using the relative sensitivity coefficient method. The results are shown in Table 2.

[0496] The measurement conditions are shown below.

[0497] Analyzer: AXIS-NOVA manufactured by KRATOS

[0498] X-ray source: monochromatized Al-Kα

[0499] X-ray source output power: 15kV, 10mA

[0500] Analysis area: 300×700μm

[0501] A neutralizing electron gun is used for charge correction during analysis.

[0502] (Cooking treatment (water filling))

[0503] The test films 1B to 3B before the retort treatment obtained in the above [Preparation of test films] were folded back in a manner such that the unstretched polypropylene film became the inner surface, and the two sides were heat-sealed to form a bag shape. Then, 70 mL of water was filled as the content, and the bag was made by heat-sealing the other side. It was retorted in a high-temperature and high-pressure retort sterilization device at 130° C. for 30 minutes. After the retort treatment, the water in the content was removed to obtain the retort treated (water-filled) test films 1B to 3B.

[0504] (oxygen permeability [mL / (m 2 ·day·MPa)])

[0505] The oxygen permeability of the test films 1B to 2B before retorting and the test films 1B to 3B after retorting (water filling) obtained by the above method was measured using OX-TRAN2 / 21 manufactured by Mocon Co., Ltd. in accordance with JIS K 7126 at a temperature of 20°C and a humidity of 90% RH. The results are shown in Table 2. It should be noted that in the table, oxygen permeability [mL / (m 2 ·day·MPa)] is called OTR.

[0506] (Water vapor permeability [g / (m 2 ·sky)])

[0507] The test films 1B to 2B before retorting treatment and the test films 1B to 3B after retorting treatment (water filling) obtained by the above method were stacked so that the unstretched polypropylene film became the inner surface, and the gas barrier laminated film was folded back and heat-sealed on three sides to form a bag shape. Calcium chloride was added as the content, and the other side was heat-sealed to form a bag with a surface area of ​​0.01 m 2 The bags were made in the same manner and placed under the conditions of 40°C and 90% RH for 300 hours. The water vapor permeability was measured using the weight difference. The results are shown in Table 2. It should be noted that in the table, the water vapor permeability [g / (m 2·day)] is called WVTR.

[0508] (Peel Strength)

[0509] The peel strengths of the test film 2B before retorting obtained by the above method and the test films 2B to 3B after retorting (water filling) were measured according to JIS Z0237 by the following method.

[0510] The gas barrier laminate in the test films 2B to 3B was peeled off from the polypropylene film or nylon film in a 180-degree direction using a tensile tester (RTA-1210A manufactured by ORIENTEC) at 23°C and a tensile speed of 300 mm / min, and the strength (N / 25 mm) at this time was taken as the peel strength. The results are shown in Table 2.

[0511] (Laminated film immersion test)

[0512] The test films 1B to 3B obtained in the above [Preparation of test films] were folded back in a manner that the unstretched polypropylene film became the inner surface, and heat-sealed to form a bag. The bagged test film was immersed in an alkaline detergent JOY (registered trademark) (manufactured by P&G) diluted 10 times with tap water. After 1 week, the test film was visually confirmed to evaluate whether delamination occurred. The results are shown in Table 2.

[0513] A: No interlayer delamination occurs

[0514] B: Delamination between layers occurs

[0515] [Table 2]

[0516]

[0517] According to Table 2, in each of the Examples, a gas barrier material having high gas barrier properties and higher peel strength than that of each of the Comparative Examples can be obtained.

[0518] Furthermore, by adding polyphosphoric acid, the water vapor permeability can be further improved.

[0519] Furthermore, by adding a cross-linking agent, the alkali resistance of the laminated film can be improved.

[0520] (Example 1C)

[0521] (1) Preparation of gas barrier coating materials

[0522] Polyacrylic acid, 10% by mass ammonia water (manufactured by Wako Pure Chemical Industries, Ltd.), and purified water were mixed so that ammonia became 250 equivalent % with respect to the carboxyl group of polyacrylic acid (manufactured by Toagosei Co., Ltd., product name: AC-10H, weight average molecular weight: 800,000), thereby obtaining an aqueous solution of ammonium polyacrylate having a concentration of 7.29% by mass.

[0523] Next, zinc oxide (manufactured by Kanto Chemical Co., Ltd.) and ammonium carbonate were added to the obtained aqueous solution of ammonium polyacrylate, mixed and stirred to prepare a mixed solution (AC). Here, the amount of zinc oxide added was set to an amount such that (the number of moles of zinc oxide in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "ZnO / PAA") became the value shown in Table 3. In addition, ammonium carbonate was set to an amount such that (the number of moles of carbonate-based ammonium salt in the gas barrier coating material) / (the number of moles of zinc oxide in the gas barrier coating material) became 1.5.

[0524] Next, polyethyleneimine (manufactured by Nippon Shokubai Co., Ltd., product name: SP-200, number average molecular weight: 10,000) was added to purified water to obtain a polyethyleneimine aqueous solution in the form of a 10% solution.

[0525] Purified water was added to oligomeric ammonium polyphosphate (manufactured by Yutian Co., Ltd., product number: water-soluble ammonium polyphosphate flame retardant NNA20, P2O5 content 59%) to prepare a 25 mass % oligomeric ammonium polyphosphate solution.

[0526] Next, the above-mentioned mixed solution (AC), the above-mentioned polyethyleneimine aqueous solution and the above-mentioned oligomeric ammonium polyphosphate solution as a phosphorus introduction source are mixed in a ratio such that (the number of moles of amino groups contained in the polyethyleneimine in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "PEI / PAA") becomes the value shown in Table 3, and (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material) (hereinafter also referred to as "P / PAA") becomes the value shown in Table 3, to prepare a mixed solution (BC).

[0527] Purified water was further added to the mixed solution (BC) so that the solid content concentration became 1.5% by mass, and the mixture was stirred until a uniform solution was obtained. Then, a surfactant (polyoxyethylene lauryl ether, manufactured by Kao Corporation, trade name: EMULGEN 120) was mixed so that the solid content of the mixed solution (BC) became 0.3% by mass, thereby preparing a gas barrier coating material.

[0528] (Comparative Examples 1C, 2C)

[0529] A gas barrier coating material was prepared in the same manner as in Example 1C except that the zinc oxide content was changed so that ZnO / PAA became the value shown in Table 3 and the oligomeric ammonium polyphosphate solution was not added.

[0530] At this time, ZnO / PAA being 0 means that zinc oxide and ammonium carbonate are not added.

[0531] (Comparative Example 3C)

[0532] A gas barrier coating material was prepared in the same manner as in Example 1C except that the 25 mass % oligomeric ammonium polyphosphate solution was changed to a 10 mass % diammonium hydrogen phosphate solution prepared by adding diammonium hydrogen phosphate ((NH 4 ) 2 HPO 4 manufactured by Kanto Chemical Co., Ltd.) to purified water.

[0533] In this case, diammonium hydrogen phosphate is not a polyphosphate compound or its salt, but in the calculation of the mixing amount, diammonium hydrogen phosphate is regarded as a polyphosphate compound or its salt, and is calculated according to (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polyacrylic acid in the gas barrier coating material). The specific mixing amount is shown as "P / PAA" in Table 3.

[0534] (Example 2C)

[0535] A gas barrier coating material was prepared in the same manner as in Example 1C except that the 25 mass % oligomeric ammonium polyphosphate solution was replaced with a 10 mass % sodium pyrophosphate solution prepared by adding sodium pyrophosphate (Na4P2O7 manufactured by Taihei Chemical Industry Co., Ltd.) to purified water.

[0536] (Example 3C)

[0537] The 25 mass % oligomeric ammonium polyphosphate solution was changed to a solution containing sodium tripolyphosphate (produced by Yoneyama Chemical Industry Co., Ltd., Na5P3O 10 ) was used to prepare a 7 mass % sodium tripolyphosphate solution, and a gas barrier coating material was prepared according to Example 1C.

[0538] (Example 4C)

[0539] The 25 mass % oligomeric ammonium polyphosphate solution was changed to a solution containing sodium tetrapolyphosphate (produced by Yoneyama Chemical Industry Co., Ltd., Na6P4O 13 ) except for the 10 mass % sodium tetrapolyphosphate solution prepared by adding the above-mentioned solvent, a gas barrier coating material was prepared according to Example 1C.

[0540] (Example 5C)

[0541] A gas barrier coating material was prepared in the same manner as in Example 1C, except that the amount of zinc oxide added was changed so that ZnO / PAA and P / PAA became the values ​​shown in Table 3, and an epoxy silane compound (manufactured by Shin-Etsu Silicone Co., Ltd., product number: KBM-403) as a cross-linking agent was mixed with the mixed solution (BC) in an amount of 0.020 mass % relative to the solid content of the mixed solution (BC).

[0542] (Example 6C)

[0543] A gas barrier coating material was prepared in the same manner as in Example 5C except that a carbodiimide compound (manufactured by Nisshinbo Chemical Co., Ltd., product number: CARBODILITE SV-02) was used as a crosslinking agent instead of the epoxysilane compound.

[0544] (Example 7C)

[0545] A gas barrier coating material was prepared in the same manner as in Example 5C except that an isocyanate compound (manufactured by Mitsui Chemicals, Inc., product number: TAKENATE (registered trademark) WD726) was used as a crosslinking agent instead of the epoxysilane compound.

[0546] (Example 8C)

[0547] A gas barrier coating material was prepared in the same manner as in Example 5C except that the amount of the oligomeric ammonium polyphosphate solution added was changed so that P / PAA became the value shown in Table 3 and the amount of the crosslinking agent added was changed to 0.015 mass %.

[0548] [Production of Gas Barrier Laminated Material]

[0549] A biaxially stretched polyethylene terephthalate film (PET12 manufactured by UNITIKA LTD.) with a thickness of 12 μm was used as a substrate. Aluminum was heated and evaporated on the corona-treated surface by high-frequency induction heating, and oxygen was introduced while vapor deposition was performed to form an aluminum oxide film with a thickness of 7 nm. Thus, an aluminum oxide vapor-deposited PET film was obtained. The water vapor permeability of the aluminum oxide vapor-deposited PET film was 1.5 g / (m 2 ·24h).

[0550] Next, the gas barrier coating material of each example and each comparative example was applied on the vapor deposited layer using a Meyer bar to a coating thickness of 0.3 μm after drying, and heat treated at 130° C. for 60 seconds using a hot air dryer to obtain a gas barrier laminate C.

[0551] [Preparation of test film]

[0552] (Preparation of Test Film 1C)

[0553] An ester adhesive (9 parts by mass of a polyurethane adhesive (manufactured by Mitsui Chemicals, Inc., trade name: TAKELACA525S), 1 part by mass of an isocyanate curing agent (manufactured by Mitsui Chemicals, Inc., trade name: TAKENATEA50), and 7.5 parts by mass of ethyl acetate) was applied on one side of a 70 μm thick unstretched polypropylene film (manufactured by Mitsui Chemicals, Inc., trade name: RXC-22). Next, the barrier surface (the surface coated with the gas barrier coating material) of the gas barrier laminate C obtained in each of the embodiments and comparative examples was attached to the surface of the unstretched polypropylene film coated with the adhesive to obtain a test film 1C before steaming treatment.

[0554] (Preparation of Test Film 2C)

[0555] An ester adhesive (9 parts by mass of a polyurethane adhesive (manufactured by Mitsui Chemicals, trade name: TAKELAC A525S), 1 part by mass of an isocyanate curing agent (manufactured by Mitsui Chemicals, trade name: TAKENATEA50), and 7.5 parts by mass of ethyl acetate) was applied on both sides of a 15 μm thick nylon film (manufactured by UNITIKA LTD., trade name: EMBLEM ONBC). Next, the barrier surface (the surface coated with the gas barrier coating material) of the gas barrier laminate C obtained in each embodiment and each comparative example and a 60 μm thick unstretched polypropylene film (manufactured by Mitsui Chemicals Tocello, Inc., trade name: RXC-22) were attached to both sides of the nylon film to which the adhesive was applied, to obtain a test film 2C before steaming treatment.

[0556] [Evaluation method]

[0557] (Appearance of gas barrier coating material and appearance of gas barrier layer)

[0558] The gas barrier coating materials obtained in each of the Examples and Comparative Examples, and the gas barrier layers in the gas barrier laminate C produced using the gas barrier coating materials were evaluated by the following methods.

[0559] The gas barrier coating materials obtained in each Example and each Comparative Example were visually evaluated on the day of production (within 1 hour after production) and 1 day after production (24 hours later) according to the following criteria.

[0560] A: No precipitation

[0561] B: There is precipitation

[0562] Furthermore, the gas barrier layer in the gas barrier laminate C produced according to the above (production of gas barrier laminate) using the gas barrier coating material obtained in each Example and each Comparative Example on the day of production (within 1 hour after production), and the gas barrier layer in the gas barrier laminate C produced in the same manner using the gas barrier coating material obtained in each Example and each Comparative Example 1 day after production (24 hours later), were visually evaluated according to the following criteria. The results are shown in Table 3.

[0563] A: There is no lumps of sediment mixed in the gas barrier layer

[0564] B: Lumps of precipitate mixed into the gas barrier layer

[0565] (XPS analysis)

[0566] The coating film surface was analyzed using a sample obtained by cutting the gas barrier layered product C obtained in each Example and each Comparative Example into a size of 1×1 cm.

[0567] The surface of the gas barrier layer (the surface coated with the gas barrier coating material) in the sample obtained by cutting the gas barrier laminate C obtained in each embodiment and each comparative example into 1×1 cm was subjected to sputtering etching based on an Ar-gas cluster ion beam source. Then, the detection element was determined by wide scanning under the following measurement conditions, and the spectrum was obtained for each element by narrow scanning. Finally, the background obtained by the Shirley method was removed from the obtained spectrum, and the atomic composition ratio (atomic%) of the detection element was calculated based on the obtained peak area using the relative sensitivity coefficient method. The results are shown in Table 3.

[0568] The measurement conditions are shown below.

[0569] Analyzer: AXIS-NOVA manufactured by KRATOS

[0570] X-ray source: monochromatized Al-Kα

[0571] X-ray source output power: 15kV, 10mA

[0572] Analysis area: 300×700μm

[0573] A neutralizing electron gun is used for charge correction during analysis.

[0574] (Cooking treatment (water filling))

[0575] The test films 1C and 2C obtained in the above [Preparation of test films] before retorting were folded back in a manner that the unstretched polypropylene film became the inner surface, and the two sides were heat-sealed to form a bag shape. Then, 70 mL of water was filled as the content, and the bag was made by heat-sealing the other side. It was retorted in a high-temperature and high-pressure retorting sterilization device at 130° C. for 30 minutes. After the retorting, the water in the content was removed to obtain the retorting (water-filled) test films 1C and 2C.

[0576] (oxygen permeability [mL / (m 2 ·day·MPa)])

[0577] The oxygen permeability of the test film 1C before the retort treatment and the test films 1C and 2C after the retort treatment (water filling) obtained by the above method was measured using OX-TRAN2 / 21 manufactured by Mocon Co., Ltd. in accordance with JIS K 7126 at a temperature of 20°C and a humidity of 90% RH. The results are shown in Table 3. It should be noted that in the table, oxygen permeability [mL / (m 2 ·day·MPa)] is called OTR.

[0578] (Water vapor permeability [g / (m 2 ·sky)])

[0579] The test film 1C before retort treatment and the test films 1C and 2C after retort treatment (water filling) obtained by the above method were overlapped so that the unstretched polypropylene film became the inner surface, and the gas barrier laminated film was folded back and heat-sealed on three sides to form a bag shape. Calcium chloride was added as the content, and the other side was heat-sealed to form a bag with a surface area of ​​0.01 m 2 The bags were made in the same manner and placed at 40°C and 90% RH for 300 hours. The water vapor permeability was measured using the weight difference. The results are shown in Table 3. It should be noted that in the table, the water vapor permeability [g / (m 2 ·day)] is called WVTR.

[0580] (Laminated film immersion test)

[0581] The test film 2C obtained in the above [Preparation of the test film] was folded back in a manner that the unstretched polypropylene film became the inner surface, and heat-sealed to form a bag. The bagged test film was immersed in an alkaline detergent JOY (registered trademark) (manufactured by P&G) diluted 10 times with tap water. After 1 week, the test film was visually confirmed to evaluate whether delamination occurred. The results are shown in Table 3.

[0582] A: No interlayer delamination occurs

[0583] B: Delamination between layers occurs

[0584] [Table 3]

[0585]

[0586] It can be understood from Table 3 that, in each example, compared with each comparative example, the barrier property is high and the application period is improved.

[0587] Furthermore, it is understood that the alkali resistance of the laminated film can be improved by adding a crosslinking agent to the gas barrier coating material.

[0588] This application claims priority based on Japanese Patent Application No. 2022-090376, Japanese Patent Application No. 2022-090386, and Japanese Patent Application No. 2022-090410, filed on June 2, 2022, the entire disclosure of which is incorporated herein.

[0589] Description of Reference Numerals

[0590] 100 Gas barrier laminate

[0591] 101 base material layer

[0592] 102 Inorganic Layer

[0593] 103 Gas barrier layer

Claims

1. A gas barrier coating material comprising a polycarboxylic acid, a polyamine compound, and a Zn compound, In the gas barrier coating material, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.40 or more and 0.70 or less. 2 . The gas barrier coating material according to claim 1 , further comprising a crosslinking agent.

3. The gas barrier coating material according to claim 2, wherein: The crosslinking agent includes one or more compounds selected from the group consisting of epoxysilane compounds, carbodiimide compounds, and isocyanate compounds.

4. The gas barrier coating material according to any one of claims 1 to 3, wherein The polycarboxylic acid includes one or more compounds selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.

5. The gas barrier coating material according to any one of claims 1 to 4, wherein The polyamine compound includes one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine). 6 . The gas barrier coating material according to claim 1 , further comprising a polyphosphoric acid compound or a salt thereof.

7. The gas barrier coating material according to claim 6, wherein In the gas barrier coating material, (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.005 to 0.

20.

8. The gas barrier coating material according to any one of claims 1 to 7, wherein In the gas barrier coating material, (the number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.40 to 0.

70.

9. A gas barrier coating material comprising a polycarboxylic acid, a polyamine compound, and a Zn compound, The cured product of the gas barrier coating material has a Zn composition ratio of 3.0 atomic % to 10.0 atomic % as measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA. 10 . The gas barrier coating material according to claim 9 , further comprising a polyphosphoric acid compound or a salt thereof.

11. The gas barrier coating material according to claim 10, wherein The cured product of the gas barrier coating material has a P composition ratio of 0.05 atomic % to 1.5 atomic % as measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA.

12. The gas barrier coating material according to any one of claims 9 to 11, wherein The polycarboxylic acid includes one or more compounds selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.

13. The gas barrier coating material according to any one of claims 9 to 12, wherein The polyamine compound includes one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine). 14 . The gas barrier coating material according to claim 9 , further comprising a crosslinking agent.

15. The gas barrier coating material according to claim 14, wherein The crosslinking agent includes one or more compounds selected from the group consisting of epoxysilane compounds, carbodiimide compounds, and isocyanate compounds.

16. A gas barrier coating material comprising a polycarboxylic acid, a polyamine compound, a Zn compound, and a polyphosphoric acid compound or a salt thereof.

17. The gas barrier coating material according to claim 16, wherein In the gas barrier coating material, (the number of moles of P contained in the polyphosphate compound or its salt in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.005 to 0.

20.

18. The gas barrier coating material according to claim 16 or 17, wherein In the gas barrier coating material, (the number of moles of the Zn compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.40 or more and 0.70 or less.

19. The gas barrier coating material according to any one of claims 16 to 18, wherein In the gas barrier coating material, (the number of moles of amino groups contained in the polyamine compound in the gas barrier coating material) / (the number of moles of -COO- groups contained in the polycarboxylic acid in the gas barrier coating material) is 0.40 to 0.

70.

20. The gas barrier coating material according to any one of claims 16 to 19, wherein The polycarboxylic acid includes one or more compounds selected from the group consisting of polyacrylic acid, polymethacrylic acid, and a copolymer of acrylic acid and methacrylic acid.

21. The gas barrier coating material according to any one of claims 16 to 20, wherein The polyamine compound includes one or more compounds selected from the group consisting of polyallylamine, polyethyleneamine, polyethyleneimine, and poly(trimethyleneimine). 22 . The gas barrier coating material according to claim 16 , further comprising a crosslinking agent.

23. The gas barrier coating material according to claim 22, wherein The crosslinking agent includes one or more compounds selected from the group consisting of epoxysilane compounds, carbodiimide compounds, and isocyanate compounds.

24. The gas barrier coating material according to any one of claims 16 to 23, wherein The cured product of the gas barrier coating material has a Zn composition ratio of 1.0 atomic % to 10.0 atomic % as measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA.

25. The gas barrier coating material according to any one of claims 16 to 24, wherein The cured product of the gas barrier coating material has a P composition ratio of 0.05 atomic % to 1.5 atomic % as measured by X-ray photoelectron spectroscopy under the conditions of X-ray source: monochromatized Al-Kα, X-ray source output: 15 kV, 10 mA.

26. A gas barrier layered product comprising a substrate layer and a gas barrier layer provided on at least one surface of the substrate layer, The gas barrier layer comprises a cured product of the gas barrier coating material according to any one of claims 1 to 25.

27. The gas barrier layered product according to claim 26, wherein The gas barrier layer has a thickness of 0.05 μm or more and 10 μm or less. 28 . The gas barrier layered product according to claim 26 , further comprising an inorganic layer between the base layer and the gas barrier layer.

29. The gas barrier layered product according to claim 28, wherein The inorganic layer is a vapor-deposited film disposed on the substrate layer, or when there is an intermediate layer between the substrate layer and the inorganic layer, the inorganic layer is a vapor-deposited film disposed on the intermediate layer, and the inorganic layer is composed of one or more inorganic substances selected from the group consisting of silicon oxide, aluminum oxide and aluminum.

Citation Information

Patent Citations

  • Gas barrier film

    JP2005225940A

  • Gas barrier film and manufacturing method

    JP2013010857A

  • Repair composition for laver-culturing column

    JP2022090376A

  • Soil property measuring method and soil property measuring device

    JP2022090386A

  • Treatment support device and treatment support method

    JP2022090410A

Cited By

  • High-barrier coating for paper bubble cap, preparation method of high-barrier coating and paper bubble cap material

    CN121519353A